Laminate, decorative material, laminate manufacturing method and laminate material selecting method
The laminate structure with a surface protective layer and transparent resin layer addresses the trade-off in conventional decorative sheets by enhancing scratch resistance and post-processing properties, ensuring minimal appearance changes.
Patent Information
- Application Number
- JP2023111344
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-06
- Publication Date
- 2025-01-20
AI Technical Summary
Conventional decorative sheets face issues with changes in appearance due to external factors such as processing and impact, exhibiting a trade-off between scratch resistance and post-processing properties.
A laminate structure comprising a surface protective layer and a transparent resin layer with specific MSE resistance values, using curable resin compositions and controlled erosion rates to enhance scratch resistance and post-processing properties.
The laminate provides improved scratch resistance, abrasion resistance, and post-processing characteristics, effectively suppressing changes in appearance.
Smart Images

Figure 2025008813000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a laminate, a decorative material using the laminate, a method for producing the laminate, and a method for selecting materials for the laminate. [Background technology]
[0002] Decorative sheets are generally used by laminating them to adherends made of metal members such as steel plates, resin members, wood members, etc., as interior or exterior materials for buildings such as floors, ceilings, walls, and entrance doors, and as fittings or fixtures such as doors, window frames, handrails, moldings, baseboards, and moldings. The decorative sheets are formed as laminates having multiple layers. The decorative sheets (laminates) are also widely used not only for the interior or exterior materials, fittings, and fixtures of buildings mentioned above, but also for surface decorative panels for cabinets in kitchens, furniture, home appliances, and office automation equipment, and for interior or exterior materials for vehicles.
[0003] 2. Description of the Related Art Conventionally, decorative sheets used, for example, in interior materials have been known that include a reinforcing layer (backer layer) for improving scratch resistance (see, for example, Patent Document 1). Furthermore, for example, decorative sheets used in exterior materials are known that have ultraviolet absorbers and radical scavengers (light stabilizers) added to the outermost layer of the laminated sheet in order to improve weather resistance (for example, Patent Document 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2014-188941 A [Patent Document 2] JP 2008-238444 A Summary of the Invention [Problem to be solved by the invention]
[0005] Decorative sheets as laminates are used for a wide range of applications as described above, but problems can arise in that the appearance changes due to various external factors such as processing when attaching the sheet to an adherend or impacts during use. However, conventional decorative sheets have the problem that, for example, when they are attached to an adherend (a substrate for decorative materials) for use, they are unable to adequately suppress changes in appearance due to various external factors such as those mentioned above.
[0006] More specifically, conventional decorative sheets tend to have poorer scratch resistance and abrasion resistance when their processing characteristics are subsequently improved. Also, conventional decorative sheets tend to have poorer scratch resistance and abrasion resistance when their processing characteristics are subsequently improved. As described above, in conventional decorative sheets, there is a so-called trade-off between post-processing characteristics and scratch resistance and abrasion resistance, and therefore there is an issue that few conventional decorative sheets have performance in all aspects of post-processing characteristics, scratch resistance, and abrasion resistance that is sufficient for use without any problems.
[0007] The present disclosure has been made in consideration of the above circumstances, and aims to provide a laminate and a decorative material that can suppress changes in the appearance of the decorative material, as well as a method for manufacturing the laminate and a method for selecting materials for the laminate. More specifically, the present disclosure aims to provide a laminate and a decorative material that have sufficient performance in terms of post-processing properties, scratch resistance, and abrasion resistance, and that is problem-free in use, as well as a method for manufacturing the laminate and a method for selecting materials for the laminate. [Means for solving the problem]
[0008] In order to solve the above problems, a laminate according to one aspect of the present disclosure is a laminate including at least a surface protection layer on a base fabric, wherein the surface protection layer includes a cured product of a curable resin composition, and the MSE resistance value MA1 obtained from the erosion rate EA1 measured using polygonal alumina particles having an average particle size (D50) of 0.3 μm is in the range of 0.05 g / μm < MA1 < 2.0 g / μm, and the MSE resistance value MB1 obtained from the erosion rate EB1 measured using spherical silica particles having an average particle size (D50) of 1.1 μm is in the range of 0.2 g / μm < MB1 < 10.0 g / μm.
[0009] Also, in order to solve the above problems, a laminate according to another aspect of the present disclosure is a laminate including at least a transparent resin layer and a surface protection layer, wherein the transparent resin layer is composed of a single layer or multiple layers, and in all layers constituting the transparent resin layer, the MSE resistance value MA2 obtained from the erosion rate EA2 measured using polygonal alumina particles having an average particle size (D50) of 1.2 μm is in the range of 1.0 g / μm < MA2 < 20.0 g / μm, and the MSE resistance value MB2 obtained from the erosion rate EB2 measured using spherical alumina particles having an average particle size (D50) of 3.0 μm is in the range of 0.1 g / μm < MB2 < 2.0 g / μm.
[0010] Also, a decorative material according to one aspect of the present disclosure is characterized by including a woody base material and the laminate of the above one aspect or the above another aspect bonded to the woody base material. Also, a decorative material according to another aspect of the present disclosure is characterized by including a base material for decorative materials and the laminate of the above one aspect or the above another aspect bonded to the base material for decorative materials.
[0011] Also, in order to solve the above problems, a method for manufacturing a laminate according to one aspect of the present disclosure is a method for manufacturing a laminate having at least a surface protection layer on a base material, wherein the surface protection layer is formed of a cured product of a curable resin composition, and the MSE resistance value MA1 obtained from the erosion rate EA1 measured using polygonal alumina particles having an average particle diameter (D50) of 0.3 μm is set within the range of 0.05 g / μm < MA1 < 2.0 g / μm, and the MSE resistance value MB1 obtained from the erosion rate EB1 measured using spherical silica particles having an average particle diameter (D50) of 1.1 μm is set within the range of 0.2 g / μm < MB1 < 10.0 g / μm.
[0012] Also, in order to solve the above problems, a method for manufacturing a laminate according to another aspect of the present disclosure is a method for manufacturing a laminate including at least a transparent resin layer and a surface protection layer, wherein the transparent resin layer is composed of a single layer or multiple layers, and in all the layers constituting the transparent resin layer, the MSE resistance value MA2 obtained from the erosion rate EA2 measured using polygonal alumina particles having an average particle diameter (D50) of 1.2 μm is set within the range of 1.0 g / μm < MA2 < 20.0 g / μm, and the MSE resistance value MB2 obtained from the erosion rate EB2 measured using spherical alumina particles having an average particle diameter (D50) of 3.0 μm is set within the range of 0.1 g / μm < MB2 < 2.0 g / μm.
[0013] Also, in order to solve the above problems, a method for selecting materials for a laminate according to one aspect of the present disclosure is a method for selecting materials for a laminate having at least a surface protection layer on a base material, wherein the surface protection layer is formed of a cured product of a curable resin composition, and the MSE resistance value MA1 obtained from the erosion rate EA1 measured using polygonal alumina particles having an average particle diameter (D50) of 0.3 μm is set within the range of 0.05 g / μm < MA1 < 2.0 g / μm, and the MSE resistance value MB1 obtained from the erosion rate EB1 measured using spherical silica particles having an average particle diameter (D50) of 1.1 μm is set within the range of 0.2 g / μm < MB1 < 10.0 g / μm.
[0014] Also, in order to solve the above problems, a method for selecting materials for a laminate according to another aspect of the present disclosure is a method for selecting materials for a laminate including at least a transparent resin layer and a surface protection layer, wherein the transparent resin layer is composed of a single layer or multiple layers, and in all layers constituting the transparent resin layer, the MSE resistance value MA2 obtained from the erosion rate EA2 measured using polygonal alumina particles with an average particle size (D50) of 1.2 μm is set within the range of 1.0 g / μm < MA2 < 20.0 g / μm, and the MSE resistance value MB2 obtained from the erosion rate EB2 measured using spherical alumina particles with an average particle size (D50) of 3.0 μm is set within the range of 0.1 g / μm < MB2 < 2.0 g / μm.
Advantages of the Invention
[0015] According to one aspect of the present disclosure, it is possible to provide a laminate and a decorative material that can suppress changes in the appearance of the decorative material, as well as a method for manufacturing the laminate and a method for selecting materials for the laminate. More specifically, according to one aspect of the present disclosure, it is possible to provide a laminate and a decorative material having performance that does not cause problems in use in all aspects of post-processing characteristics, scratch resistance, and abrasion resistance, as well as a method for manufacturing the laminate and a method for selecting materials for the laminate.
Brief Description of the Drawings
[0016] [Figure 1] It is a cross-sectional view showing a schematic configuration of a decorative sheet according to an embodiment of the present disclosure. [Diagram 2] It is a cross-sectional view showing a schematic configuration of a decorative sheet according to a first modification of an embodiment of the present disclosure. [Diagram 3] It is a cross-sectional view showing an example of a configuration of a decorative material according to a second modification of an embodiment of the present disclosure. [Figure 4] It is a cross-sectional view showing another example of a configuration of a decorative material according to a second modification of an embodiment of the present disclosure.
Modes for Carrying Out the Invention
[0017] Hereinafter, the decorative sheet and decorative member according to the embodiment of the present disclosure will be described with reference to the drawings. Here, the drawings are schematic, and the relationship between thickness and planar dimensions, the thickness ratio of each layer, etc. are different from the actual ones. As long as it is within the scope of the present disclosure, it is not necessary to stack in the order shown in the drawings. In addition, layers not shown in the drawings may be added. In addition, the embodiments shown below are examples of configurations for embodying the technical idea of the present disclosure, and the technical idea of the present disclosure is not limited to the materials, shapes, structures, etc. of the components described below. The technical idea of the present disclosure can be modified in various ways within the technical scope defined by the claims described in the claims.
[0018] In addition, the directions of "left and right" and "up and down" in the following description are merely defined for the convenience of explanation and do not limit the technical ideas of the present disclosure. Therefore, for example, if the page is rotated 90 degrees, "left and right" and "up and down" are read interchangeably, and if the page is rotated 180 degrees, "left" becomes "right" and "right" becomes "left".
[0019] As a result of intensive research, the present inventors have found that by providing a surface protection layer having a specific MSE (micro-slurry jet erosion) resistance value M and a transparent resin layer in a decorative sheet, the decorative sheet, which is a laminate, can be sufficiently provided with the necessary post-processing properties, scratch resistance, impact resistance, etc. as performance. As a result, the present inventors have invented a decorative sheet that is sufficiently provided with the necessary scratch resistance, abrasion resistance, post-processing properties, and impact resistance as performance, and can suppress changes in the appearance of the decorative material surface, and a decorative material equipped with the decorative sheet. The MSE resistance value M is a value defined by the reciprocal of the erosion rate E (i.e., M=1 / E). In other words, the MSE resistance value M is a value calculated from the erosion rate E. Therefore, a layer with a large MSE resistance value M means that the layer is relatively difficult to scrape, and a layer with a small MSE resistance value M means that the layer is relatively easy to scrape. A first embodiment of the present disclosure (hereinafter, referred to as "the present embodiment") will be described below with reference to the drawings.
[0020] (Measurement of erosion rates EA1 and EB1) First, the "erosion rate E" required to calculate the "MSE resistance value M" defined in this embodiment will be described. The erosion rate E in this embodiment is a value measured using, for example, a material surface precision testing machine (micro slurry jet erosion tester, hereinafter referred to as MSE tester, manufactured by Palmeso Co., Ltd. / device name Nano MSE / model N-MSE-A). A specific method for measuring the erosion rate E is as follows.
[0021] The erosion rates EA1 and EB1 in this embodiment are the erosion rates E of the surface protective layer 4, and are distinguished from the erosion rates EA2 and EB2 of the transparent resin layers 1 and 2 and are referred to as "erosion rates EA1 and EB1." The measurement method of the erosion rates EA1 and EB1 differs from the measurement method of the erosion rate E in the type of particles used and the standard projection force X. When measuring the erosion rate EA1, polygonal alumina particles with an average particle size (D50) of 0.3 μm are used. More specifically, polygonal alumina particles with an average particle size (D50) of 0.3 μm are dispersed in water to prepare a slurry containing 1% by mass of polygonal alumina particles relative to the total mass of the slurry. When measuring the erosion rate EB1, spherical silica particles with an average particle size (D50) of 1.1 μm are used. More specifically, spherical silica particles with an average particle size (D50) of 1.1 μm are dispersed in water to prepare a slurry containing 1% by mass of spherical silica particles relative to the total mass of the slurry.
[0022] Next, the decorative sheet is fixed to a stand, and the projection distance between the decorative sheet and the nozzle for spraying each of the above slurries is set to 4 mm. The nozzle diameter is 1 mm x 1 mm. A slurry containing polygonal alumina particles or spherical silica particles is sprayed from the nozzle, and the decorative sheet fixed to the stand is cut in sequence from the surface protection layer. The spray strength at this time is determined based on the standard projection force X, which is calculated in advance by cutting an existing hardness standard piece, Si wafer, or PMMA substrate under similar experimental conditions and calculating the cut displacement relative to the spray amount of the slurry (i.e., the depth cut when 1 g of slurry is sprayed). In this embodiment using polygonal alumina particles and spherical silica particles, the standard projection force X is the projection force when 0.481 μm / g is cut from the existing hardness standard piece Si wafer for polygonal alumina particles, and the projection force when 1.86 μm / g is cut from the existing hardness standard piece PMMA for spherical silica particles.
[0023] In the present embodiment, the erosion rates EA1 and EB1 are measured for the protective surface layer. Therefore, in the measurement method, cutting is performed sequentially from the protective surface layer as described above. After washing the cut portion with water, the depth of the cut, i.e., the erosion depth Z, is measured. The erosion depth Z is measured, for example, using a stylus surface profiler (manufactured by Kosaka Laboratory Co., Ltd. / Model PU-EU1 / stylus tip R=2-10 μm / load 100 or 200 μN / measurement magnification 10,000-20,000 / measurement length 3-6 mm / measurement speed 0.2 mm / sec). In this embodiment, the erosion rate E [μm / g] is calculated using the amount of projected particles X' [g] calculated from the above-mentioned projection force and the erosion depth Z [μm].
[0024] In this embodiment, for convenience, the MSE resistance value obtained from the erosion rate EA1 measured using polygonal alumina particles having an average particle size (D50) of 0.3 μm is defined as "MA1", and the MSE resistance value obtained from the erosion rate EB1 measured using spherical silica particles having an average particle size (D50) of 1.1 μm is defined as "MB1".
[0025] Moreover, the erosion rates EA2 and EB2 in this embodiment are the erosion rates of the transparent resin layer, and are referred to as "erosion rates EA2 and EB2" to distinguish them from the erosion rates EA1 and EB1 of the surface protective layer 4. The measurement methods for the erosion rates EA2 and EB2 differ from the measurement method for the erosion rate E in the type of particles used and the standard projection force X. When measuring the erosion rate EA2, polygonal alumina powder with an average particle size D50 = 1.2 μm is dispersed in water to prepare a slurry containing 3 mass% of polygonal alumina powder relative to the total mass of the slurry. When measuring the erosion rate EB2, spherical alumina powder with an average particle size D50 = 3.0 μm is dispersed in water to prepare a slurry containing 3 mass% of spherical alumina powder relative to the total mass of the slurry.
[0026] Next, the decorative sheet is fixed to a stand, and the projection distance between the decorative sheet and the nozzle for spraying each of the above slurries is set to 4 mm. The nozzle diameter is 1 mm x 1 mm. A slurry containing polygonal alumina powder or spherical alumina powder is sprayed from the nozzle, and the decorative sheet fixed to the stand is cut in sequence from the surface protection layer. The spray strength at this time is determined based on the standard projection force X, which is calculated in advance by cutting an existing hardness standard piece, Si wafer, or HRC-45 under similar experimental conditions and calculating the cut displacement relative to the amount of slurry sprayed (i.e., the depth cut when 1 g of slurry is sprayed). In this embodiment using polygonal alumina powder and spherical alumina powder, the standard projection force X is the projection force when 6.36 μm / g is cut from the existing hardness standard piece Si wafer for polygonal alumina particles, and the projection force when 1.0 μm / g is cut from the existing hardness standard piece HRC-45 for spherical alumina particles.
[0027] Other than that, the erosion rates are the same as the erosion rates EA1 and EB1 described above, so detailed description will be omitted. Note that the erosion rates EA2 and EB2 in this embodiment are measured for the transparent resin layer. Therefore, in the measurement method, the cutting may be performed sequentially from the surface protective layer as described above, or the transparent resin layer before the formation of the surface protective layer may be sequentially cut.
[0028] In this embodiment, for the sake of convenience, the erosion rate measured using polygonal alumina particles having an average particle size (D50) of 1.2 μm is defined as "EA2", and the erosion rate measured using spherical alumina particles having an average particle size (D50) of 3.0 μm is defined as "EB2". In addition, in this embodiment, for convenience, the MSE resistance value obtained from the erosion rate EA2 measured using polygonal alumina particles having an average particle size (D50) of 1.2 μm is defined as "MA2", and the MSE resistance value obtained from the erosion rate EB2 measured using spherical alumina particles having an average particle size (D50) of 3.0 μm is defined as "MB2".
[0029] It is also known that the erosion rate E is not affected by the magnitude of the erosion rate E of the lower layer present in the depth direction when measuring the erosion rate E. Therefore, when measuring the erosion rates EA1 and EB1, the MSE test may be performed starting from the surface protective layer located on the outermost surface, and when measuring the erosion rates EA2 and EB2, the MSE test may be performed starting from the surface protective layer located on the outermost surface.
[0030] (Composition of decorative sheet) Hereinafter, each component of the decorative sheet (one example of a laminate) of this embodiment will be described. Note that this embodiment will be described assuming that the transparent resin layer is a single layer.
[0031] The decorative sheet 10 shown in Fig. 1 is a laminate comprising multiple layers, including, from the top of the drawing, a surface protective layer 4, a transparent resin layer 1, an adhesive layer 5 (heat-sensitive adhesive layer, anchor coat layer, dry lamination adhesive layer), a picture design layer 6, a concealing layer 3, a base fabric layer 7, and an easy-adhesion layer 8. The base fabric layer 7 is a layer that serves as the base material for the decorative sheet 10, and is also referred to as a base material sheet. More specifically, the decorative sheet 10 according to this embodiment is a decorative sheet having a configuration in which a picture pattern layer 6 and a concealing layer 3 are provided on one side of a transparent resin layer 1, and a surface protection layer 4 is provided on the other side of the transparent resin layer 1. As shown in Fig. 1, the decorative sheet 10 has a transparent resin layer 1 provided on an original fabric layer 7, and an adhesive layer 5 and a picture pattern layer 6 provided between the original fabric layer 7 and the transparent resin layer 1. As a result, the decorative sheet 10 has good adhesion between the transparent resin layer 1 and the original fabric layer 7, and can be used as a surface material that can decorate the surface layer of a substrate to be adhered.
[0032] The decorative sheet 10 according to this embodiment may be a laminate including at least a transparent resin layer 1. For example, the decorative sheet 10 may be a laminate including a transparent resin layer 1 and one or more layers selected from the group consisting of a surface protective layer 4, an adhesive layer 5, a picture pattern layer 6, a concealing layer 3, a base fabric layer 7, and an easy-adhesion layer 8. The decorative sheet 10 may also be a laminate including at least the transparent resin layer 1 and the surface protective layer 4.
[0033] In order to improve the design, an embossed pattern may be appropriately provided on the surface of the transparent resin layer 1 on the side of the surface protective layer 4 . The total thickness of the decorative sheet 10 is preferably within the range of 60 μm to 250 μm. If the total thickness is less than 60 μm, there is a concern that the required performance of the decorative sheet may be reduced in terms of concealment (ability to hide the underlying surface of the wood substrate) and scratch resistance. If the total thickness is greater than 250 μm, there is a concern that the cost may increase and that the workability may be reduced when bonding the decorative sheet to the wood substrate. Moreover, the decorative sheet of the present embodiment preferably does not contain vinyl chloride resin. By using a decorative sheet that uses a non-vinyl chloride resin, concerns about the generation of toxic gases and the like during incineration can be reduced. Hereinafter, each layer constituting the decorative sheet of this embodiment will be described in detail.
[0034] (Original layer) When the decorative sheet is to be given design, scratch resistance and post-processing resistance, the raw cloth layer (raw cloth) 7 may be appropriately selected from, for example, paper such as tissue paper, titanium paper, and resin-impregnated paper, synthetic resins such as polyethylene, polypropylene, polystyrene, polybutylene, polycarbonate, polyester, polyethylene terephthalate, polybutylene terephthalate, polyamide, ethylene-vinyl acetate copolymer, polyvinyl alcohol, and acrylic, or foams of these synthetic resins, rubbers such as ethylene-propylene copolymer rubber, ethylene-propylene-diene copolymer rubber, styrene-butadiene-styrene block copolymer rubber, and polyurethane, organic or inorganic nonwoven fabrics, synthetic paper, and metal foils such as aluminum, iron, gold, and silver. The raw cloth layer 7 may also be a sheet made of the same resin composition as the transparent resin layer 1. Of the above, it is preferable to use polyolefin-based materials such as polypropylene and polyethylene.
[0035] Examples of the polyolefin resin contained in the raw fabric layer 7 include polypropylene, polyethylene, polybutene, and the like, as well as α-olefins (e.g., propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene, 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1-pentene, 4-ethyl These include homopolymers or copolymers of two or more types of α-olefins (e.g., 1-ethyl-1-hexene, 3-ethyl-1-hexene, 9-methyl-1-decene, 11-methyl-1-dodecene, 12-ethyl-1-tetradecene, etc.) as well as copolymers of ethylene or α-olefins with other monomers, such as ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, ethylene-methyl methacrylate copolymer, ethylene-ethyl methacrylate copolymer, ethylene-butyl methacrylate copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, and ethylene-butyl acrylate copolymer.
[0036] When a substrate having an inactive surface such as a polyolefin-based material is used as the raw fabric layer 7, it is preferable to perform, for example, corona treatment, plasma treatment, ozone treatment, electron beam treatment, ultraviolet treatment, dichromate treatment, etc. on the front and back sides of the raw fabric layer 7. Furthermore, a primer layer (not shown) may be provided between the raw fabric layer 7 and the picture pattern layer 6 to ensure adhesion.
[0037] When it is desired to provide the decorative sheet with a concealing property, a concealing colored sheet may be used for the original fabric layer 7, or as shown in FIG. 1, a concealing layer 3 may be provided on the original fabric layer 7 and below the picture pattern layer 6. The concealing layer 3 will be described later. When a colored sheet is used as the original fabric layer 7, a coloring agent may be added to the resin material constituting the original fabric layer 7 to color it. As the coloring agent, for example, inorganic pigments (titanium oxide, carbon black, etc.) and organic pigments (phthalocyanine blue, etc.) as well as dyes can be used. The coloring agent of this embodiment can be selected from one or more known or commercially available coloring agents, and the amount added can be adjusted so as to obtain the desired concealing property and design property.
[0038] If necessary, various additives such as fillers, foaming agents, flame retardants, lubricants, antistatic agents, antioxidants, crystal nucleating agents, UV absorbers, light stabilizers, heat stabilizers, colorants, and matting agents may be added to the raw fabric layer 7. The thickness of the raw fabric layer 7 is preferably within the range of 20 μm to 150 μm, taking into consideration printing workability, costs, and the like.
[0039] (Pattern layer) The picture pattern layer 6 may be formed on the base layer 7 or the transparent resin layer 1 by, for example, gravure printing, offset printing, screen printing, flexographic printing, electrostatic printing, ink jet printing, or the like. When ink is used to form the picture pattern layer 6, the binder contained in the ink may be appropriately selected from, for example, nitrocellulose, cellulose, vinyl chloride-vinyl acetate copolymer, polyvinyl butyral, polyurethane, acrylic, polyester, etc., either alone or modified. These may be water-based, solvent-based, or emulsion type, and may be either a one-component type or a two-component type using a hardener. Furthermore, the ink can be cured by exposure to ultraviolet light, electron beams, etc. The most common method is to use a urethane-based ink and cure it with an isocyanate.
[0040] In addition to the binder, the picture pattern layer 6 may contain pigments, colorants such as dyes, extender pigments, solvents, and various additives contained in normal inks. Particularly commonly used pigments include condensed azo, insoluble azo, quinacridone, isoindoline, anthraquinone, imidazolone, cobalt, phthalocyanine, carbon, titanium oxide, iron oxide, and pearl pigments such as mica. In addition to applying ink, it is also possible to apply designs by deposition or sputtering of various metals. The thickness of the picture pattern layer 6 is preferably within the range of 0.5 μm to 10 μm.
[0041] (Hidden layer) The concealing layer 3 can be provided on the original fabric layer 7 or on the pattern layer 6 formed on the transparent resin layer 1 by the same printing method as that for the picture pattern layer 6. When providing the concealing layer 3, for example, a comma coater, a knife coater, a lip coater, metal vapor deposition, or a sputtering method may be used. The concealing layer 3 is generally provided as an upper layer of the original fabric layer 7 and as a lower layer of the picture pattern layer 6.
[0042] The material used for the concealing layer 3 may basically be the same as that for the picture pattern layer 6. Since the concealing layer 3 must have a concealing property as its purpose, it is preferable to use, for example, an opaque pigment, titanium oxide, iron oxide, etc. as a pigment. In addition, it is also possible to add metals such as gold, silver, copper, and aluminum to improve the concealing property. Generally, flake-shaped aluminum is often added. If the coating thickness, i.e., the thickness of the concealing layer 3, is less than 2 μm, it is difficult to impart concealing property, and if it exceeds 10 μm, the cohesive force of the resin layer tends to be weak. For this reason, the thickness of the concealing layer 3 is preferably in the range of 2 μm to 10 μm.
[0043] (adhesive layer) For the adhesive layer 5, any material can be selected. Examples of the bonding method using the adhesive layer 5 include thermal lamination, extrusion lamination, dry lamination, etc. The adhesive contained in the adhesive layer 5 can be selected from materials such as acrylic, polyester, polyurethane, etc. The adhesive contained in the adhesive layer 5 is usually preferably of a two-component curing type due to its cohesive force, and it is particularly desirable to use a urethane-based material obtained by the reaction of a polyol using isocyanate.
[0044] (Transparent resin layer) The transparent resin layer 1 is formed on the adhesive layer 5. By having specific erosion rates EA2 and EB2, the transparent resin layer 1 has excellent scratch resistance, post-processing characteristics, and impact resistance, and it becomes possible to provide a decorative sheet capable of suppressing the appearance change of the decorative material. Hereinafter, the transparent resin layer 1 in the present embodiment will be described in detail.
[0045] The transparent resin layer 1 is composed of a single layer or multiple layers. In all the layers constituting the transparent resin layer 1, the MSE resistance value MA2 obtained from the above-mentioned erosion rate EA2 measured using polygonal alumina powder with an average particle size (D50) of 1.2 μm is in the range of more than 1.0 g / μm and less than 20.0 g / μm (1.0 g / μm < MA2 < 20.0 g / μm), and the MSE resistance value MB2 obtained from the erosion rate EB2 measured using spherical alumina particles with an average particle size (D50) of 3.0 μm is in the range of more than 0.1 g / μm and less than 2.0 g / μm (0.1 g / μm < MB2 < 2.0 g / μm). When the MSE resistance value MA2 of the transparent resin layer 1 is 1.0 g / μm or less, the post-processing characteristics and impact resistance tend to decrease significantly. Also, when the MSE resistance value MA2 of the transparent resin layer 1 is 20.0 g / μm or more, the scratch resistance tends to decrease significantly.
[0046] Also, when the MSE resistance value MB2 of the transparent resin layer 1 is 0.1 g / μm or less, the post-processing characteristics and impact resistance tend to decrease significantly. Also, when the MSE resistance value MB2 of the transparent resin layer 1 is 2.0 g / μm or more, the scratch resistance tends to decrease significantly.
[0047] In the decorative sheet 10 of this embodiment, as described above, the transparent resin layer 1 has an MSE resistance value MA2 in the range of more than 1.0 g / μm and less than 20.0 g / μm, and an MSE resistance value MB2 in the range of more than 0.1 g / μm and less than 2.0 g / μm, making it possible to provide a decorative sheet that has excellent scratch resistance, post-processing properties and impact resistance and can suppress changes in the appearance of the decorative material.
[0048] In addition, from the viewpoint of improving scratch resistance and post-processing characteristics, etc., in the transparent resin layer 1, it is more preferable that the MSE resistance value MA2 is in the range of more than 1.0 g / μm and less than 15.0 g / μm, and the MSE resistance value MB2 is in the range of more than 0.1 g / μm and less than 1.0 g / μm.
[0049] That is, the transparent resin layer 1 is composed of a resin adjusted so that the MSE resistance value MA2 is in the range of more than 1.0 g / μm and less than 20.0 g / μm, and the MSE resistance value MB2 is in the range of more than 0.1 g / μm and less than 2.0 g / μm. Furthermore, it is more preferable that the transparent resin layer 1 is composed of a resin adjusted so that the MSE resistance value MA2 is in the range of more than 1.0 g / μm and less than 15.0 g / μm, and the MSE resistance value MB2 is in the range of more than 0.1 g / μm and less than 1.0 g / μm. By making the MSE resistance value MA2 less than 15.0 g / μm, good scratch resistance can be obtained. Also, by making the MSE resistance value MB2 less than 1.0 g / μm, good scratch resistance can be obtained.
[0050] The MSE resistance value M can be controlled, for example, by the selection of the material of the transparent resin layer 1 or the process conditions during formation. The crystallinity of the crystalline polypropylene resin can be controlled by a known method using process conditions. For example, when the transparent resin layer 1 is formed of a crystalline polypropylene resin, the process conditions can be controlled by controlling the heating during film formation to increase the crystallinity and increase the MSE resistance value M, or decrease the crystallinity and decrease the MSE resistance value M.
[0051] By controlling the degree of crystallinity through the selection of the material for the transparent resin layer 1 and the process conditions during formation, the above-mentioned MSE resistance value MA2 can be set within the range of more than 1.0 g / μm and less than 20.0 g / μm, and the MSE resistance value MB2 can be set within the range of more than 0.1 g / μm and less than 2.0 g / μm.
[0052] The transparent resin layer 1 is formed on the adhesive layer 5 as described above. The transparent resin layer 1 may be a sheet formed by film formation, or may be a laminate of already formed sheets. The transparent resin layer 1 is preferably formed using a polyolefin resin. Specifically, it is preferable to use a polypropylene resin as the transparent resin layer 1. The transparent resin layer 1 is formed, for example, of a highly crystalline polypropylene resin. Furthermore, one or both surfaces of the transparent resin layer 1 may be activated, for example, by corona treatment, plasma treatment, electron beam treatment, ultraviolet treatment, dichromate treatment, or the like, as necessary.
[0053] When the transparent resin layer 1 is formed from a sheet by film formation, for example, a method using an extruder is generally used. When the transparent resin layer 1 is laminated and formed, there is no particular restriction, and for example, a method using heat and pressure, an extrusion lamination method, a dry lamination method, etc. are generally used. In addition, when the embossed pattern 1a is applied, there is a method of embossing a sheet that has been once laminated by various methods, for example, by heat and pressure, or a method of providing an uneven pattern on a cooling roll and embossing the sheet at the same time as extrusion lamination using the cooling roll. More specifically, the embossed pattern 1a is directly applied to the transparent resin layer 1, for example, a highly crystalline polypropylene sheet, and the method includes a method of providing an embossed pattern on the sheet formed by film formation using an embossing plate having an uneven pattern by heat and pressure, and a method of providing an embossment at the same time as cooling using a cooling roll having an uneven pattern when forming a film using an extruder. Here, it is also possible to embed ink in the embossed pattern 1a as the embossed part to further improve the design. The embossed pattern 1a may be provided if necessary, but may not be provided if unnecessary.
[0054] The thickness of the transparent resin layer 1 is preferably in the range of 40 μm or more and 170 μm or less. If the thickness of the transparent resin layer 1 is less than 40 μm, the weather resistance and scratch resistance may decrease. If the thickness of the transparent resin layer 1 exceeds 170 μm, the manufacturing cost may increase and the post-processing property may decrease. If necessary, various additives such as heat stabilizers, flame retardants, ultraviolet absorbers, light stabilizers, antiblocking agents, catalyst scavengers, and, as long as the characteristics of this embodiment are not impaired, colorants, light scattering agents, and gloss adjusters may also be added to the transparent resin layer 1.
[0055] It is common to add, in any combination, heat stabilizers such as phenols, sulfurs, phosphorus, and hydrazines, flame retardants such as aluminum hydroxide and magnesium hydroxide, ultraviolet absorbers such as benzotriazoles, benzoates, benzophenones, and triazines, and light stabilizers such as hindered amines. In particular, when used for this purpose, weather resistance must be considered. In that case, an ultraviolet absorber and a light stabilizer may be added to the transparent resin layer 1, and the appropriate amount of each is within the range of 0.1% by mass to 2.0% by mass, with the transparent resin layer 1 being 100% by mass. The transparent resin layer 1 may also contain a crystal nucleating agent (nano-sized nucleating agent) that has been subjected to vesicle treatment by supercritical reverse phase evaporation.
[0056] In addition, the crystalline polypropylene resin forming the transparent resin layer 1 can be appropriately selected and designed from isotactic polypropylene, syndiotactic polypropylene, random polypropylene, lock polypropylene, and mixtures thereof, each having a different pentad fraction. More preferably, it is important that the crystalline polypropylene resin is a propylene homopolymer, i.e., a highly crystalline homopolypropylene resin, which is a homopolymer, having an isotactic pentad fraction (mmmm fraction) of 95% or more, more preferably 96% or more. In addition, resins other than the crystalline polypropylene constituting the transparent resin layer 1 can be appropriately selected depending on the purpose of the blending, as long as they do not significantly adversely affect the physical properties of the crystalline polypropylene. However, in order to maintain the V-groove bending processability, it is preferable that the resin has good compatibility with the crystalline polypropylene resin constituting the transparent resin layer 1. The material of the transparent resin layer 1 is not limited to this, and a highly flexible polyolefin resin such as a random polypropylene resin containing an ethylene content or a polyolefin thermoplastic elastomer can be used.
[0057] The terms used in the above description of the transparent resin layer 1 will be briefly explained below. A nucleating agent is added to promote the generation of crystal nuclei during the crystallization of a resin, or to make the nucleating agent itself a crystal nucleus. Nucleating agents include melting agents that melt into the resin of the base material when added and precipitate again to generate crystal nuclei, and non-melting agents that do not melt when added to the base material and become crystal nuclei with the same particle size. Examples of nucleating agents for polypropylene resin include metal phosphate salts, metal benzoate salts, metal pimelate salts, metal rosin salts, benzylidene sorbitol, quinacridone, cyanine blue, and talc. In particular, in this embodiment, in order to maximize the effect of the nano-processing, it is preferable to use metal phosphate salts, metal benzoate salts, metal pimelate salts, and metal rosin salts that are non-melting and can be expected to have good transparency, but if the nano-processing can make the material transparent, colored quinacridone, cyanine blue, talc, etc. can also be used. In addition, melting benzylidene sorbitol may be appropriately mixed with the non-melting nucleating agent.
[0058] The isotactic pentad fraction (mmmm fraction) is calculated from a numerical value (electromagnetic wave absorption rate) obtained by resonating the resin material constituting the transparent resin layer 1 at a predetermined resonance frequency by 13C-NMR measurement (nuclear magnetic resonance measurement) using carbon C (nuclear species) with a mass number of 13, and specifies the atomic arrangement, electronic structure, and molecular microstructure in the resin material. The isotactic pentad fraction of a polypropylene resin is the ratio of five propylene units lined up as determined by 13C-NMR, and is used as a measure of crystallinity or stereoregularity. Such an isotactic pentad fraction is one of the important factors that mainly determine the scratch resistance of the surface, and basically, the higher the isotactic pentad fraction, the higher the crystallinity of the sheet, and therefore the better the scratch resistance.
[0059] (Surface protective layer) The surface protective layer 4 is a layer provided to impart functions such as weather resistance, scratch resistance, stain resistance, and designability to the decorative sheet 10. As will be described in detail later, the curable resin composition that forms the surface protective layer 4 has a specific MSE resistance value M, which can impart excellent processing characteristics, abrasion resistance, and scratch resistance to the decorative sheet 10. The surface protective layer 4 may contain various additives, such as an ultraviolet absorbing agent, a heat stabilizer, a light stabilizer, an antiblocking agent, a catalyst trap, a colorant, a light scattering agent, and a gloss adjusting agent, if necessary.
[0060] A curable resin composition can be used as a material forming the surface protective layer 4. In this embodiment, the surface protective layer 4 contains a cured product of the curable resin composition. More specifically, the curable resin composition constituting the surface protective layer 4 is preferably formed containing at least one of a resin that is cured by heat, i.e., a thermosetting resin, and a resin that is cured by ultraviolet light or electron beam irradiation, i.e., an ionizing radiation curable resin. In other words, the surface protective layer 4 may be formed containing only a thermosetting resin as the curable resin composition, or may be formed containing only an ionizing radiation curable resin. Furthermore, the surface protective layer 4 may be formed containing both a thermosetting resin and an ionizing radiation curable resin, i.e., a mixed composition of a thermosetting resin and an ionizing radiation curable resin.
[0061] The thermosetting resin used for the surface protective layer 4 can be appropriately selected from, for example, polyurethane, acrylic, acrylic silicone, fluorine, epoxy, vinyl, polyester, melamine, aminoalkyd, urea, etc. The form can be any of water-based, emulsion, and solvent-based, and the curing can be either a one-liquid type or a two-liquid type using a curing agent. Among them, a urethane-based top coat using an isocyanate reaction is preferable from the viewpoints of workability, cost, cohesive strength of the resin itself, etc.
[0062] Specifically, it is preferable to use an acrylic urethane resin in which an acrylic polyol is combined with an isocyanate curing agent as the thermosetting resin used for the surface protective layer 4. In other words, it is preferable that the thermosetting resin constituting the surface protective layer 4 is composed of an acrylic polyol (an acrylic polyol compound) and an isocyanate curing agent.
[0063] The isocyanate can be appropriately selected from curing agents such as adducts, biurets, and isocyanurates, which are derivatives of tolylene diisocyanate (TDI), xylylene diisocyanate (XDI), hexamethylene diisocyanate (HMDI), diphenylmethane diisocyanate (MDI), lysine diisocyanate (LDI), isophorone diisocyanate (IPDI), bis(isocyanatomethyl)cyclohexane (HXDI), trimethylhexamethylene diisocyanate (TMDI), and various prepolymers. However, in consideration of weather resistance, it is preferable to use a curing agent based on hexamethylene diisocyanate (HMDI) or isophorone diisocyanate (IPDI), which have a linear molecular structure.
[0064] The ionizing radiation curable resin used in the surface protective layer 4 can be appropriately selected from, for example, polyester acrylate, epoxy acrylate, urethane acrylate, acrylic acrylate, etc., but it is particularly preferable to use urethane acrylate and acrylic acrylate resins, which have good weather (light) resistance. As a curing method for the ionizing radiation curable resin, curing with active energy rays such as ultraviolet rays and electron beams is preferable from the viewpoint of workability. As an electron beam source, for example, light sources such as ultra-high pressure mercury lamps, high pressure mercury lamps, low pressure mercury lamps, carbon arc lamps, black lights, metal halide lamps, etc. can be used. The wavelength of the ultraviolet rays is preferably within the range of 180 nm to 400 nm.
[0065] It is more preferable to use, for example, a mixture of a urethane-based resin obtained by reacting an acrylic polyol with an isocyanate as the thermosetting resin and a urethane acrylate-based resin as the ionizing radiation curable resin as the mixture of thermosetting resin and ionizing radiation curable resin for the surface protective layer 4. By using a mixture of a thermosetting resin and an ionizing radiation curable resin, it is possible to improve the surface hardness and at least one of the suppression of cure shrinkage and the adhesion of inorganic fine particles (inorganic filler).
[0066] Moreover, the ionizing radiation curable resin constituting the surface protective layer 4 is preferably an ultraviolet curable resin that is cured by ultraviolet rays. The ultraviolet curing resin constituting the surface protective layer 4 preferably has 4 or more functional groups and contains one or more components with a mass average molecular weight of 500 or more. More preferably, the ultraviolet curing resin has 4 or more functional groups and contains one or more components with a mass average molecular weight in the range of 500 to 5,000. If the ultraviolet curing resin has less than 4 functional groups, the crosslinking density is low and the scratch resistance is significantly reduced, which is not preferable. If the ultraviolet curing resin has a mass average molecular weight of less than 500, the surface condition during coating is significantly deteriorated, which is not preferable. If the ultraviolet curing resin has a mass average molecular weight of more than 5,000, the viscosity of the coating liquid increases and the coating suitability is significantly reduced, which is not preferable.
[0067] The amount of the photoinitiator added is not particularly limited, and is preferably about 0.1 to 15 parts by mass with respect to 100 parts by mass of the base resin. The type of photoinitiator is not particularly limited. In the case of a resin system having a radical polymerizable unsaturated group, at least one of the following photoinitiators can be selected: acetophenones, benzophenones, thioxanthones, benzoin, benzoin methyl ether, Michler's benzoyl benzoate, Michler's ketone, diphenyl sulfide, dibenzyl disulfide, diethyl oxide, triphenyl biimidazole, isopropyl-N,N dimethylaminobenzoate, etc. In addition, it is desirable to design a combination of multiple types according to the light source and production environment.
[0068] In the case of a resin system having a cationic polymerizable functional group, the photoinitiator can be selected from at least one of, for example, aromatic diazonium salts, aromatic sulfonium salts, metallocene compounds, benzoin sulfonic acid esters, and furyloxysulfoxonium diallyliodosyl salts.
[0069] The method for forming the surface protective layer 4 is not particularly limited, and the surface protective layer 4 may be formed by coating the above-mentioned material in a coating liquid form using a conventional method such as gravure coating, microgravure coating, comma coating, knife coating, or die coating, and then curing the liquid using a method suitable for the resin material, such as thermal curing or ultraviolet curing. This surface protective layer 4 may be provided on the transparent resin layer 1 after bonding the picture pattern layer 6 provided on the original fabric layer 7 to the transparent resin layer 1 via the adhesive layer 5, or may be provided on the transparent resin layer 1 before bonding the transparent resin layer 1 to the original fabric layer 7.
[0070] Furthermore, in order to improve weather resistance, an ultraviolet absorber and a light stabilizer may be appropriately added to the surface protective layer 4. In addition, functional additives such as antibacterial agents and antifungal agents may be added as desired to impart various functions. Note that, in this embodiment, the surface protective layer 4 is formed from a resin containing a mixture of an ionizing radiation curable resin and a thermosetting resin, or a resin containing only a thermosetting resin, but this embodiment is not limited to this. For example, the surface protective layer 4 may be a layer formed only from an ionizing radiation curable resin.
[0071] In order to improve the scratch resistance of the surface or to adjust the luster (luster) associated with imparting design properties, it is desirable to add an inorganic filler as a luster adjuster to the surface protective layer 4 . Examples of inorganic fillers to be added to the surface protective layer 4 include alumina, silica, boehmite, iron oxide, magnesium oxide, aluminosilicate, diamond, silicon nitride, silicon carbide, glass beads, calcium titanate, barium titanate, magnesium pyroporate, zinc oxide, silicon nitride, zirconium oxide, chromium oxide, iron oxide, and glass fibers. As the inorganic filler, inorganic fine particles having an average particle size of 1 μm or more and 30 μm or less can be used, and inorganic fine particles having an average particle size of 1 μm or more and 10 μm or less are particularly suitable. When the average particle size of the inorganic filler is less than 1 μm, it tends to be difficult to obtain a matte effect. This is because, in order to achieve a matte effect, it is ideal for the particle size to be the same as or larger than the thickness of the film (layer) to which the inorganic filler is added. When the average particle size of the inorganic filler exceeds 30 μm, or more reliably, 10 μm, the inorganic filler is likely to fall off from the surface protective layer 4 under high load conditions, and the luster tends to change and the surface tends to look worse.
[0072] For example, when gravure printing is selected as the method for forming the surface protective layer 4, the appropriate coating thickness for one layer is usually within the range of 2 μm to 15 μm. In this case, as described above, it is preferable to select an inorganic filler having an average particle size of about the same size as the thickness that can be applied at one time.
[0073] The content of the inorganic filler in the surface protective layer 4 is preferably within a range of 1 part by mass to 20 parts by mass with respect to 100 parts by mass of the resin constituting the surface protective layer 4. If the content of the inorganic filler is less than 1 part by mass, scratch resistance may decrease. If the content of the inorganic filler exceeds 20 parts by mass, the surface gloss may decrease significantly, which may impair the design and decrease weather resistance and stain resistance.
[0074] It is desirable to perform a surface treatment on the inorganic filler contained in the surface protective layer 4. By performing a surface treatment on the inorganic filler, it is possible to strengthen the bond with the surface protective layer 4. Note that the surface protective layer 4 may contain inorganic fillers whose surfaces are not treated.
[0075] In addition, when carrying out the surface treatment, it is desirable that the inorganic filler has a functional group that hydrophobizes the surface of the inorganic filler and imparts reactivity with the surface protective layer 4. In other words, it is desirable that the surface treatment agent used to treat the surface of the inorganic filler has a reactive group that reacts with the main resin that constitutes the surface protective layer 4. When carrying out the surface treatment of the inorganic filler, the method is not particularly limited, and a known method can be selected.
[0076] The surface treatment agent used for the surface treatment of the inorganic filler may be at least one of a surfactant, a fatty acid metal salt, a silane coupling agent, silicone, wax, and a modified resin. The surface treatment agent of this embodiment may be, for example, a silicone oil type, an alkylsilazane type, a trimethylsilylating agent, an alkoxysilane type, a siloxane, a silane coupling agent, a titanium coupling agent, a phosphoric acid type, or a fatty acid type surfactant, and may be one type or a combination of multiple types.
[0077] Examples of silicone oil-based treatment agents that can be selected include straight silicone oils (dimethyl silicone oil, methylphenyl silicone oil, etc.) and modified silicone oils (amino-modified, epoxy-modified, carboxyl-modified, carbinol-modified, methacryl-modified, mercapto-modified, phenol-modified, one-end reactive modified, heterogeneous functional group-modified, polyether-modified, methylstyryl-modified, alkyl-modified, higher fatty acid ester-modified, specially hydrophilic modified, higher alkoxy-modified, higher fatty acid-containing modified, fluorine-modified silicone oil, etc.).
[0078] As the alkylsilazane-based treatment agent, for example, hexamethyldisilazane, vinylsilazane, etc. can be selected. Examples of the silane coupling agent include alkoxysilane compounds such as methyltrimethoxysilane, dimethyldimethoxysilane, trimethylmethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, trimethylethoxysilane, n-hexyltrimethoxysilane, n-hexyltriethoxysilane, n-hexyltriethoxysilane, n-octyltriethoxysilane, n-hexyltriethoxysilane, decyltriethoxysilane, phenyltriethoxysilane, benzyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, diethoxymethylphenylsilane, allyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, aminopropyltriethoxysilane, and aminopropyltrimethoxysilane; and chlorosilane compounds such as trimethylchlorosilane and diethyldichlorosilane.
[0079] As the trimethylsilylation agent, an alkoxysilane compound among silane coupling agents can be selected. Examples of titanate coupling agents that can be selected include isopropyl tridecylbenzenesulfonyl titanate, isopropyl tris(dioctyl pyrophosphate) titanate, tetraisopropyl bis(dioctyl phosphite) titanate, tetraoctyl bis(ditridecyl phosphite) titanate, tetra(2,2-diallyloxymethyl-1-butyl) bis(ditridecyl) phosphite titanate, and bis(dioctyl pyrophosphate) oxyacetate titanate. As the aluminate-based coupling agent, for example, acetoalkoxyaluminum diisopropylate can be selected.
[0080] When an embossed pattern 1a is applied to the surface of the transparent resin layer 1 on the side of the surface protective layer 4, the ink forming the surface protective layer 4 can be embedded into this embossed pattern by wiping processing to improve the design. In terms of weather resistance, in order to protect the transparent resin layer 1 as the base material, there is also a method of imparting weather resistance to the surface protective layer 4 and the transparent resin layer 1 respectively as described above. Moreover, not only that, there is also a method of adding an ultraviolet absorber and a light stabilizer to the adhesive layer 5 and the pattern layer 6 itself respectively in order to protect the pattern layer 6.
[0081] In FIG. 1, an example in which the surface protective layer 4 is a single layer was described, but in the decorative sheet 10 according to the present embodiment, the surface protective layer 4 is not limited to a single layer. The surface protective layer 4 may be a single layer or may have a multilayer structure. That is, the surface protective layer 4 may be composed of one or more layers. Therefore, the surface protective layer 4 may have an overall thickness within the range of 2 μm or more and 21 μm or less. Further, when the surface protective layer 4 has a multilayer structure, the inorganic filler as a gloss adjuster may be contained in one or more of the multilayer structures.
[0082] Further, when the surface protective layer 4 is multilayered, at least the outermost layer may be composed of a mixed composition of a thermosetting resin and a radiation-curable resin, or may contain a thermosetting resin, and layers formed of different types of resin materials may be included in a plurality of layers.
[0083] 〔MSE Resistance Values MA1 and MB1 of the Surface Protective Layer〕 The surface protective layer 4 contains a cured product of a curable resin composition, and the MSE resistance value MA1 obtained from the erosion rate EA1 measured using polygonal alumina particles having an average particle size (D50) of 0.3 μm is more than 0.05 g / μm and less than 2.0 g / μm (0.05 g / μm < MA1 < 2.0 g / μm), and the MSE resistance value MB1 obtained from the erosion rate EB1 measured using spherical silica particles having an average particle size (D50) of 1.1 μm is more than 0.2 g / μm and less than 10.0 g / μm (0.2 g / μm < MB1 < 10.0 g / μm). That is, the cured product of the curable resin composition forming the surface protective layer 4 has the MSE resistance value MA1 within the range of more than 0.05 g / μm and less than 2.0 g / μm, and the MSE resistance value MB1 within the range of more than 0.2 g / μm and less than 10.0 g / μm.
[0084] When the MSE resistance value MA1 of the surface protective layer 4 is 0.05 g / μm or less or the MSE resistance value MB1 is 0.2 g / μm or less, the MSE resistance values MA1 and MB1 are small, and there is a tendency for inferior scratch resistance and abrasion resistance. Also, when the MSE resistance value MA1 of the surface protective layer 4 is 2.0 g / μm or more or the MSE resistance value MB1 is 10.0 g / μm or more, the processing characteristics (e.g., V-cut processability, bend processability) may deteriorate.
[0085] Also, in the surface protective layer 4, the MSE resistance value MB1 may be in the range of more than 0.2 g / μm and less than 2.0 g / μm (0.2 g / μm < MB1 < 2.0 g / μm). By setting the MSE resistance value MB1 to less than 2.0 g / μm, the processing characteristics (e.g., post-processing characteristics) can be more reliably improved. Also, by setting the MSE resistance value MB1 of the surface protective layer 4 to more than 0.2 g / μm, the scratch resistance and abrasion resistance can be reliably improved.
[0086] Thus, in the decorative sheet 10 according to this embodiment, the surface protective layer 4 has the MSE resistance value MA1 in the range of more than 0.05 g / μm and less than 2.0 g / μm and the MSE resistance value MB1 in the range of more than 0.2 g / μm and less than 10.0 g / μm as described above, whereby it is possible to provide a decorative sheet having excellent processing characteristics (e.g., post-processing characteristics) and scratch resistance and abrasion resistance and capable of suppressing appearance changes of the decorative material.
[0087] Also, when the surface protective layer 4 has a multilayer structure, it is sufficient that the average value of the entire surface protective layer 4 has the above-specified MSE resistance values MA1 and MB1.
[0088] (Easy adhesion layer) The easy adhesion layer 8 is a layer for bonding the adherend (e.g., the base material for the decorative material) of the decorative sheet 10 and the base web layer 7, and is also referred to as a primer layer. The material used for the easy-adhesion layer 8 may basically be the same as that for the picture pattern layer 6 and the concealing layer 3. In addition, considering that the easy-adhesion layer 8 is wound in a web shape to be applied to the back surface of the decorative sheet, inorganic fillers such as silica, alumina, magnesia, titanium oxide, barium sulfate, etc. may be added to the easy-adhesion layer 8 to avoid blocking and improve adhesion with the adhesive. The coating thickness, i.e., the thickness of the easy-adhesion layer 8 (primer layer) is intended to ensure adhesion with the base material layer 7, so that it is appropriate to be in the range of 0.1 μm to 10.0 μm, more preferably in the range of 0.1 μm to 3.0 μm. The easy-adhesion layer 8 is necessary when the base layer 7 has an inactive surface such as an olefin-based material, but is not particularly necessary when the surface is active.
[0089] (1.1) First Modification A first modified example of the decorative sheet according to the present embodiment will be described with reference to Fig. 2. Fig. 2 is a schematic cross-sectional view for explaining one configuration example of a decorative sheet 20 according to the first modified example of the present embodiment. The decorative sheet 20 according to this modified example differs from the decorative sheet 10 according to the present embodiment described above in that the transparent resin layer is not a single layer but a multi-layer.
[0090] The decorative sheet shown in Fig. 2 comprises, in order from the top of the drawing, a surface protective layer 4, a transparent resin layer 11, an adhesive layer 5 (heat-sensitive adhesive layer, anchor coat layer, dry lamination adhesive layer), a picture pattern layer 6, a concealing layer 3, a base fabric layer 7, and an easy-adhesion layer 8. As will be described in detail later, the transparent resin layer 11 has a multilayer structure and comprises a transparent resin layer 1 and a transparent resin layer 2.
[0091] More specifically, the decorative sheet 20 according to this modification is a decorative sheet having a structure in which a picture pattern layer 6 and a concealing layer 3 are provided on one side (transparent resin layer 2 side) of a transparent resin layer 11 having a multi-layer structure, and a surface protection layer 4 is provided on the other side (transparent resin layer 1 side) of the transparent resin layer 11. As shown in FIG. 2, the decorative sheet 20 has a transparent resin layer 11 provided on an original fabric layer 7, and an adhesive layer 5 and a picture pattern layer 6 provided between the original fabric layer 7 and the transparent resin layer 11. As a result, the decorative sheet 20 has good adhesion between the transparent resin layer 11 and the original fabric layer 7, and can be used as a surface material that can decorate the surface layer of a substrate to be adhered. The decorative sheet 20 according to this embodiment may be a laminate including at least the transparent resin layer 11 and the surface protection layer 4.
[0092] Below, a detailed description will be given of the transparent resin layer 11, which is a configuration of the decorative sheet 20 that differs from that of the decorative sheet 10. Note that the configuration of the decorative sheet 20 other than the transparent resin layer 11 is the same as that of the decorative sheet 10. For this reason, the same reference numerals as those in the decorative sheet 10 are used and detailed description will be omitted.
[0093] (Transparent resin layer) As shown in Fig. 2, the decorative sheet 20 has a transparent resin layer 11. The transparent resin layer 11 has a multi-layer structure (two layers in this example) and is composed of a transparent resin layer 1 and a transparent resin layer 2. More specifically, the transparent resin layer 11 is composed of multiple layers, and has the transparent resin layer 1 which is a first transparent resin layer in contact with the surface protective layer 4, and the transparent resin layer 2 which is a second transparent resin layer in contact with the transparent resin layer 1.
[0094] [First transparent resin layer] The transparent resin layer 1, which is the first transparent resin layer of the transparent resin layer 11 in this modified example, has the same configuration as the transparent resin layer 1 of the decorative sheet 10 in the present embodiment described above, and therefore is given the same symbol and detailed description is omitted. In this modification, for convenience, the MSE resistance value MA2 of the transparent resin layer 1, which is the first transparent resin layer, is referred to as the “MSE resistance value MA 2-1 ". Also, the MSE resistance value MB2 of the first transparent resin layer 1 is referred to as "MSE resistance value MB 2-1" MSE resistance value MA 2-1 and MSE resistance value MB 2-1 The measurement methods for these resistances are the same as those for the MSE resistance value MA2 and the MSE resistance value MB2, and therefore the explanation will be omitted.
[0095] In this modification, the transparent resin layer 1 has an erosion rate EA measured using polygonal alumina particles having an average particle size (D50) of 1.2 μm, similarly to the above embodiment. 2-1 The MSE resistance value obtained from MA 2-1 is more than 1.0g / μm and less than 20.0g / μm (1.0g / μm <MA 2-1 <20.0g / μm) and the erosion rate EB measured using spherical alumina particles with an average particle size (D50) of 3.0 μm 2-1 The MSE resistance value MB obtained from 2-1 More than 0.1g / μm and less than 2.0g / μm (0.1g / μm <MB 2-1 <2.0 g / μm). In other words, the transparent resin layer 1 may have an MSE resistance value of MA 2-1 is adjusted to be within the range of more than 1.0 g / μm and less than 20.0 g / μm, and the MSE resistance value MB 2-1 The transparent resin layer 1 may be made of a resin adjusted so that the MSE resistance value MA 2-1 is more than 1.0 g / μm and less than 15.0 g / μm, and the MSE resistance value MB 2-1 It is more preferable that the resin be adjusted so that the viscosity is more than 0.1 g / μm and less than 1.0 g / μm.
[0096] [Second transparent resin layer] 2, in the decorative sheet 20 according to this modification, the transparent resin layer 2, which is the second transparent resin layer, is provided between the transparent resin layer 1, which is the first transparent resin layer, and the adhesive layer 5. In other words, the transparent resin layer 2 is located below the transparent resin layer 1. The transparent resin layer 2 may be provided when further laminate strength is required, particularly when the transparent resin layer is formed by the extrusion lamination method.
[0097] Like the transparent resin layer 1, the transparent resin layer 2 has a specific MSE resistance value M, which makes it possible to provide a decorative sheet that has excellent scratch resistance and post-processing properties and is capable of suppressing changes in the appearance of the decorative material. Here, for convenience, the MSE resistance value MA2 of the transparent resin layer 2 is referred to as the "MSE resistance value MA 2-2 ". Also, the MSE resistance value MB2 of the transparent resin layer 2 is referred to as "MSE resistance value MB 2-2 " MSE resistance value MA 2-2 and MSE resistance value MB 2-2 The measurement method for each of the above MSE resistance values MA2, MA 2-1 And the above MSE resistance values MB2, MB 2-1 Since this is equivalent to the above, the explanation will be omitted.
[0098] The transparent resin layer 2 has an erosion rate EA measured using polygonal alumina particles having an average particle size (D50) of 1.2 μm. 2-2 The MSE resistance value obtained from MA 2-2 is more than 1.0g / μm and less than 20.0g / μm (1.0g / μm <MA 2-2 <20.0g / μm) and the erosion rate EB measured using spherical alumina particles with an average particle size (D50) of 3.0 μm 2-2 The MSE resistance value MB obtained from 2-2 More than 0.1g / μm and less than 2.0g / μm (0.1g / μm <MB 2-2 <2.0 g / μm). In other words, the transparent resin layer 2 may have an MSE resistance value of MA 2-2 is adjusted to be within the range of more than 1.0 g / μm and less than 20.0 g / μm, and the MSE resistance value MB 2-2 The thickness of the resin may be adjusted to be within the range of more than 0.1 g / μm and less than 2.0 g / μm. MSE resistance value MA of transparent resin layer 2 2-2 When the MSE resistance value is 1.0g / μm or less, 2-2 When the MSE resistance value MA of the transparent resin layer 2 is less than 0.1 g / μm, the post-processing properties and impact resistance tend to be significantly deteriorated. 2-2 If the MSE resistance value is 20.0 g / μm or more, 2-2If the surface roughness is 2.0 g / μm or more, the scratch resistance tends to decrease significantly.
[0099] In this way, in the decorative sheet 20 according to this embodiment, the transparent resin layer 1, which is the first transparent resin layer constituting the transparent resin layer 11, has an erosion rate EA measured using polygonal alumina particles having an average particle size (D50) of 1.2 μm. 2-1 The MSE resistance value obtained from MA 2-1 The erosion rate EB measured using spherical alumina particles with an average particle size (D50) of 3.0 μm is in the range of more than 1.0 g / μm and less than 20.0 g / μm. 2-1 The MSE resistance value MB obtained from 2-1 In the transparent resin layer 2 which is the second transparent resin layer, the erosion rate EA measured using polygonal alumina particles having an average particle size (D50) of 1.2 μm may be in the range of more than 0.1 g / μm and less than 2.0 g / μm. 2-2 The MSE resistance value obtained from MA 2-2 The erosion rate EB measured using spherical alumina particles with an average particle size (D50) of 3.0 μm is in the range of more than 1.0 g / μm and less than 20.0 g / μm. 2-2 The MSE resistance value MB obtained from 2-2 may be in the range of more than 0.1 g / μm and less than 2.0 g / μm. This makes it possible to provide a decorative sheet that has excellent scratch resistance, post-processing properties and impact resistance, and is capable of suppressing changes in the appearance of the decorative material.
[0100] In general, the transparent resin layer 1 and the transparent resin layer 2 in the transparent resin layer 11 are laminated and formed by a co-extrusion method. The resin contained in the transparent resin layer 2 is preferably, for example, an acid-modified resin such as polypropylene, polyethylene, or an acrylic resin. For the purpose of improving adhesive strength, the thickness of the transparent resin layer 2 is desirably 2 μm or more. If the thickness of the transparent resin layer 2 is less than 2 μm, it tends to be difficult to obtain sufficient adhesive strength.
[0101] Moreover, the thickness of the transparent resin layer 2 is desirably 20 μm or less. If the thickness of the transparent resin layer 2 exceeds 20 μm, the transparent resin layer 2 tends to deteriorate during long-term use, causing cohesive failure and making it prone to peeling. In other words, the thickness of the transparent resin layer 2 is preferably within the range of 2 μm or more and 20 μm or less.
[0102] In addition, in the transparent resin layer 11, the sum of the thickness of the transparent resin layer 1 and the thickness of the transparent resin layer 2 is preferably 40 μm or more and 170 μm or less. In other words, the total thickness of the transparent resin layer 11 is preferably 40 μm or more and 170 μm or less. This makes it possible to suppress an increase in manufacturing costs and a decrease in post-processing properties while improving weather resistance and scratch resistance.
[0103] (1.2) Second Modification A decorative material according to a second modified example of this embodiment of the present disclosure will be described with reference to Fig. 3. The decorative sheet according to this embodiment can be suitably used for the purpose of producing a decorative material (for example, a decorative material for floors) by laminating it with a wood substrate as a substrate for the decorative material. Fig. 3 is a cross-sectional view for explaining one configuration example of the decorative material 100 according to the second modified example of this embodiment of the present disclosure.
[0104] As shown in Fig. 3, the decorative material 100 according to this modification is obtained by laminating the decorative sheet 10 according to this embodiment onto a wooden substrate 16 so that the surface protective layer 4 of the decorative sheet 10 is the outermost layer. That is, the decorative material 100 differs from the decorative sheet 10 according to the first embodiment in that it includes an adhesive 15 and a wooden substrate 16.
[0105] (Decorative materials) 3, in the decorative material 100, a concealing layer 3, a picture pattern layer 6, an adhesive layer 5, a transparent resin layer 1, and a surface protection layer 4 are laminated in this order on one surface of an original fabric layer 7 in a decorative sheet 10, and an easy-adhesion layer 8, an adhesive 15, and a wood base material 16 are provided on the other surface of the original fabric layer 7. In other words, the decorative material 100 comprises a wood base material 16 and a decorative sheet 10 which is a laminate bonded to the wood base material 16. This makes it possible to provide a decorative material 100 that has excellent processing characteristics (for example, post-processing characteristics), scratch resistance, abrasion resistance, and impact resistance, and that is capable of suppressing changes in appearance.
[0106] (wood base material) A wood board is used as the wood base material 16. More specifically, examples of wood boards include chipboards and wood fiber boards (MDF, HDF, etc.). Also, a combination of these chipboards or wood fiber boards with a wood veneer or wood plywood may be used as the wood base material 16.
[0107] For example, in the decorative material 100, when chipboard (ten-point average roughness Rzjis: about 80 to 250 μm) or a composite substrate having such chipboard on the surface is used as the material of the wooden substrate 16, it is possible to suppress the remaining of air bubbles between the decorative sheet 10 and the wooden substrate 16 using such chipboard. Furthermore, the decorative material 100 using such chipboard as the wooden substrate 16 can exhibit good impact resistance, abrasion resistance, and walking feel. The ten-point average roughness Rzjis is a value measured by a measurement method conforming to JIS B0601-2001.
[0108] The shape of the wood base material 16 may be a flat plate, taking into consideration that the decorative material 100 is usually installed as a floor material (flooring). An adhesive 15 can be used to bond the wooden substrate 16 and the decorative sheet 10 together. As the adhesive 15, for example, a known adhesive containing polyvinyl acetate, polyvinyl chloride, vinyl chloride-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ionomer, butadiene-acrylonitrile rubber, neoprene rubber, natural rubber, urethane-based reactive hot melt adhesive (PUR), etc. as an active ingredient can be used. When bonding the wooden substrate 16 and the decorative sheet 10 together, a bonding device such as a cold press, hot press, roll press, laminator, wrapping, edge bonding machine, or vacuum press can be used.
[0109] After joining the wood base material 16 and the decorative sheet 10, depending on the characteristics of the final product, it may be cut, tongued using a tenon, V-grooved, chamfered on all four sides (e.g., C-chamfered), etc.
[0110] The decorative material 100 according to this modification may have grooves and / or chamfers extending from the decorative sheet 10 side to the wood substrate 16, and the grooves and chamfers may be painted with a colored paint. The colored paint for painting the grooves and chamfers can be, for example, an ink made by dissolving or dispersing a colorant (organic pigment, inorganic pigment) that can also be used in the adhesive layer 5 in a vehicle. Specific examples of colorants are the same as those described above. Examples of vehicles include chlorinated polyolefins such as chlorinated polyethylene and chlorinated polypropylene, polyesters, polyurethanes made of isocyanates and polyols, polyacrylics, polyvinyl acetates, polyvinyl chlorides, vinyl chloride-vinyl acetate copolymers, cellulose-based resins, polyamide-based resins, and the like. These vehicles can be used alone or in combination of two or more. As described above, it is preferable to use a colored paint containing a curing agent such as isocyanate that chemically bonds with the silanol groups of the modified resin layer. In addition, solvents, auxiliary agents, and the like can be added as necessary.
[0111] The decorative material 100 according to this modification has been described above. Note that FIG. 3 illustrates an example in which the decorative material 100 is constructed using the decorative sheet 10 according to the present embodiment, but the present disclosure is not limited thereto. The decorative material 100 may be constructed using the decorative sheet 20 according to the first modification of this embodiment, as shown in FIG. 4. For example, the decorative material 100 may have a concealing layer 3, a picture pattern layer 6, an adhesive layer 5, a transparent resin layer 2, a transparent resin layer 1, and a surface protection layer 4 laminated in this order on one side of the original fabric layer 7 in the decorative sheet 20, and an easy-adhesion layer 8, an adhesive 15, and a wood base material 16 provided on the other side of the original fabric layer 7.
[0112] That is, the decorative material 100 may be configured to include a wooden substrate 16 and a decorative sheet 20 that is a laminate bonded to the wooden substrate 16. This makes it possible to provide the decorative material 100 that has excellent scratch resistance and impact resistance and is capable of suppressing changes in appearance.
[0113] (Effects of this embodiment) The decorative sheet and decorative material according to this embodiment have the following effects. (1) The decorative sheet 10 of this embodiment is a laminate having at least a surface protective layer 4 on an original fabric layer 7, wherein the surface protective layer 4 comprises a cured product of a curable resin composition, and the MSE resistance value MA1 obtained from the erosion rate EA1 measured using polygonal alumina particles having an average particle size (D50) of 0.3 μm is in the range of more than 0.05 g / μm and less than 2.0 g / μm, and the MSE resistance value MB1 obtained from the erosion rate EB1 measured using spherical silica particles having an average particle size (D50) of 1.1 μm is in the range of more than 0.2 g / μm and less than 10.0 g / μm. According to this configuration, it is possible to provide a decorative sheet (laminate) that has excellent processing characteristics (for example, post-processing characteristics) and scratch resistance and abrasion resistance, and that can suppress changes in the appearance of the decorative material.
[0114] (2) In the decorative sheet 10 according to this embodiment, the surface protective layer 4 may have an MSE resistance value MB1 in the range of more than 0.2 g / μm and less than 2.0 g / μm. According to this configuration, it is possible to more reliably improve processing characteristics (e.g., post-processing characteristics), and also to reliably improve scratch resistance and abrasion resistance, thereby providing a decorative sheet (laminate) that can suppress changes in the appearance of the decorative material.
[0115] (3) The decorative sheet 10 of this embodiment is a laminate including at least a transparent resin layer 1 and a surface protective layer 4, and the transparent resin layer 1 is composed of a single layer, and the MSE resistance value MA2 obtained from the erosion rate EA2 measured using polygonal alumina particles having an average particle size (D50) of 1.2 μm is in the range of more than 1.0 g / μm and less than 20.0 g / μm, and the MSE resistance value MB2 obtained from the erosion rate EB2 measured using spherical alumina particles having an average particle size (D50) of 3.0 μm is in the range of more than 0.1 g / μm and less than 2.0 g / μm. According to this configuration, it is possible to provide a decorative sheet (laminate) that has excellent scratch resistance and post-processing properties and is capable of suppressing changes in the appearance of the decorative material.
[0116] (4) The decorative sheet 20 according to the present embodiment is a laminate including at least a transparent resin layer 11 and a surface protective layer 4, the transparent resin layer 11 being composed of multiple layers, and having a transparent resin layer 1 which is a first transparent resin layer in contact with the surface protective layer 4, and a transparent resin layer 2 which is a second transparent resin layer in contact with the transparent resin layer 1, the erosion rate EA of the transparent resin layer 1 measured using polygonal alumina particles having an average particle size (D50) of 1.2 μm 2-1 The MSE resistance value obtained from MA 2-1 The erosion rate EB measured using spherical alumina particles with an average particle size (D50) of 3.0 μm is in the range of more than 1.0 g / μm and less than 20.0 g / μm. 2-1 The MSE resistance value MB obtained from 2-1 is in the range of more than 0.1 g / μm and less than 2.0 g / μm, and the erosion rate EA measured using polygonal alumina particles having an average particle size (D50) of 1.2 μm in the transparent resin layer 2 2-2 The MSE resistance value obtained from MA 2-2 The erosion rate EB measured using spherical alumina particles with an average particle size (D50) of 3.0 μm is in the range of more than 1.0 g / μm and less than 20.0 g / μm. 2-2 The MSE resistance value MB obtained from 2-2 is in the range of more than 0.1 g / μm and less than 2.0 g / μm. According to this configuration, it is possible to provide a decorative sheet (laminate) that has excellent scratch resistance and post-processing properties and can suppress changes in the appearance of the decorative material.
[0117] (5) In the decorative sheets 10, 20 according to this embodiment, the transparent resin layers 1, 11 may have an MSE resistance value MA2 in the range of more than 1.0 g / μm and less than 15.0 g / μm, and an MSE resistance value MB2 in the range of more than 0.1 g / μm and less than 1.0 g / μm. According to this configuration, it is possible to provide a decorative sheet (laminate) that has even better scratch resistance and post-processing properties and can suppress changes in the appearance of the decorative material.
[0118] (6) In the decorative sheets 10, 20 according to this embodiment, the transparent resin layers 1, 11 have a thickness of 40 μm or more and 170 μm or less. According to this configuration, it is possible to suppress an increase in manufacturing costs and a decrease in post-processing properties while improving weather resistance and scratch resistance.
[0119] (7) In the decorative sheets 10, 20 according to the present embodiment, the transparent resin layers 1, 11 contain a polyolefin resin. According to this configuration, a decorative sheet (laminate) can be obtained that is made of materials that are environmentally friendly and have good processing suitability.
[0120] (8) The decorative sheets 10, 20 according to this embodiment include a surface protective layer 4, and the surface protective layer 4 contains a mixed composition of a thermosetting resin and an ionizing radiation curable resin, or a thermosetting resin. According to this configuration, by using the above-mentioned mixed composition, it is possible to improve the surface hardness, suppress the cure shrinkage, and improve at least one of the adhesion of the inorganic fine particles (inorganic filler). In addition, by using a thermosetting resin, it is possible to improve the light resistance, suppress the increase in the production cost, and improve the workability and the resin cohesive force.
[0121] (9) The cosmetic sheets 10 and 20 according to this embodiment have a transparent resin layer 1, 11 provided on the base fabric layer 7, and an adhesive layer 5 and a pattern layer 6 are provided between the base fabric layer 7 and the transparent resin layer 1, 11. According to this configuration, the cosmetic sheets 10 and 20 have good adhesion between the transparent resin layer 1, 11 and the base fabric layer 7, and can be used as a decorative material capable of decorating the surface layer of a substrate serving as an adherend.
[0122] (10) The decorative material 100 according to this embodiment includes a woody base material 16 and a cosmetic sheet 10, 20 which is a laminate bonded to the woody base material 16. According to this configuration, it is possible to provide a decorative material having excellent scratch resistance and impact resistance and capable of suppressing appearance changes.
[0123] Hereinafter, a manufacturing method of the laminate (cosmetic sheet) according to this embodiment and its modification will be described. The manufacturing method of the laminates 10 and 20 according to this embodiment and its modification is a manufacturing method of a laminate having at least a surface protection layer 4 on the base fabric 7, wherein the surface protection layer 4 is formed of a cured product of a curable resin composition, and the MSE resistance value MA1 obtained from the erosion rate EA1 measured using polygonal alumina particles having an average particle diameter (D50) of 0.3 μm is set within the range of 0.05 g / μm < MA1 < 2.0 g / μm, and the MSE resistance value MB1 obtained from the erosion rate EB1 measured using spherical silica particles having an average particle diameter (D50) of 1.1 μm is set within the range of 0.2 g / μm < MB1 < 10.0 g / μm. According to the above manufacturing method, the laminates 10 and 20 (cosmetic sheets) according to the above-described embodiment and its modification can be obtained. Therefore, it is possible to obtain a laminate having performance that does not cause problems in use in terms of all of post-processing characteristics, scratch resistance, and abrasion resistance.
[0124] Further, the method for manufacturing the laminates 10 and 20 according to the present embodiment and its modified examples is at least a method for manufacturing a laminate including the transparent resin layers 1 and 11 and the surface protection layer 4, wherein the transparent resin layers 1 and 11 are formed as a single layer or multiple layers, and in all of the transparent resin layers 1 and 2, the MSE resistance value MA2 obtained from the erosion rate EA2 measured using polygonal alumina particles with an average particle size (D50) of 1.2 μm is set within the range of 1.0 g / μm < MA2 < 20.0 g / μm, and the MSE resistance value MB2 obtained from the erosion rate EB2 measured using spherical alumina particles with an average particle size (D50) of 3.0 μm is set within the range of 0.1 g / μm < MB2 < 2.0 g / μm. According to the above manufacturing method, the laminates 10 and 20 (cosmetic sheets) according to the present embodiment and its modified examples described above can be obtained. Therefore, a laminate having performance that does not cause problems in use in terms of post-processing characteristics and scratch resistance can be obtained.
[0125] Hereinafter, the materials constituting the laminates 10 and 20 (cosmetic sheets) according to the present embodiment and its modified examples described above and the method for selecting them will be described. Conventionally, in order to obtain a laminate (cosmetic sheet) having target physical properties (performance, characteristics), mainly the types of materials constituting the laminate (cosmetic sheet) and their contents have been adjusted. That is, the design concept (design method) of the conventional laminate (cosmetic sheet) mainly involved adjusting the types of materials and their contents.
[0126] In contrast, the design concept (design method) of the laminate (cosmetic sheet) according to each of the above embodiments is to obtain a laminate (cosmetic sheet) having target physical properties (performance, characteristics) by setting the MSE resistance value M of at least one of the surface protection layer and the transparent resin layer within a specific range. Thus, the method for selecting the materials constituting the laminate (cosmetic sheet) according to each of the above embodiments is significantly different from the conventional design concept (design method).
[0127] Specifically, the method for selecting materials for the laminates 10 and 20 (cosmetic sheets) according to the present embodiment and its modified examples is a method for selecting materials for a laminate having at least a surface protection layer 4 on a base fabric 7. The surface protection layer 4 is formed of a cured product of a curable resin composition, and the MSE resistance value MA1 obtained from the erosion rate EA1 measured using polygonal alumina particles with an average particle size (D50) of 0.3 μm is set within the range of 0.05 g / μm < MA1 < 2.0 g / μm. Also, the MSE resistance value MB1 obtained from the erosion rate EB1 measured using spherical silica particles with an average particle size (D50) of 1.1 μm is set within the range of 0.2 g / μm < MB1 < 10.0 g / μm. With the above material selection method, the laminates 10 and 20 (cosmetic sheets) according to the present embodiment and its modified examples described above can be obtained. Therefore, a laminate having performance that does not cause problems in use in terms of all of post-processing characteristics, scratch resistance, and abrasion resistance can be obtained.
[0128] Also, the method for selecting materials for the laminates 10 and 20 (cosmetic sheets) according to the present embodiment and its modified examples is a method for selecting materials for a laminate including at least a transparent resin layer 1, 11 and a surface protection layer 4. The transparent resin layer 1, 11 is composed of a single layer or multiple layers. For all of the transparent resin layers 1, 2, the MSE resistance value MA2 obtained from the erosion rate EA2 measured using polygonal alumina particles with an average particle size (D50) of 1.2 μm is set within the range of 1.0 g / μm < MA2 < 20.0 g / μm. Also, the MSE resistance value MB2 obtained from the erosion rate EB2 measured using spherical alumina particles with an average particle size (D50) of 3.0 μm is set within the range of 0.1 g / μm < MB2 < 2.0 g / μm. With the above material selection method, the laminates 10 and 20 (cosmetic sheets) according to the present embodiment and its modified examples described above can be obtained. Therefore, a laminate having performance that does not cause problems in use in terms of post-processing characteristics and scratch resistance can be obtained.
[0129] (Example) Examples of decorative sheets according to embodiments of the present disclosure (hereinafter, also referred to as "Examples") will be described below. Note that the embodiments of the present disclosure are not limited to the following examples. In this example, coating materials A to G were used as coating materials for forming the surface protective layer. The hardness of the surface protective layer in this example (MSE resistance value MA1, MSE resistance value MB1, erosion rate EA1, erosion rate EB1) was controlled by the formulation of each of the above coating materials. The compositions of the materials (ionizing radiation curable resin, thermosetting resin, and curing agent) used in coating materials A to G are shown in Tables 1 to 3. In this example, an acrylate compound was used as the ionizing radiation curable resin, and an acrylic polymer was used as the thermosetting resin. Each coating material will be described in detail below.
[0130] [Table 1]
[0131] [Table 2]
[0132] [Table 3]
[0133] <Coating Agent A> [Main ingredient] Coating agent A was composed of ionizing radiation curable resin 1 shown in Table 1 (an acrylate compound having tetra- to penta-functionality and a mass average molecular weight Mw of 2300) as the main component. [Prescription] Coating agent A was prepared by mixing the following additives with 100 parts by mass of the above-mentioned main agent. UV absorber "Tinuvin 479 (BASF): 5 parts by weight Light stabilizer "Tinuvin 123 (BASF)": 5 parts by weight Ethyl acetate as dilution solvent: 50 parts by weight Gloss adjuster: Silica 730 (manufactured by Fuji Silica): 15 parts by weight
[0134] <Paint B> [Main ingredient] Coating agent B was composed of a resin material consisting of a mixture of ionizing radiation curable resin 2 (an acrylate compound having 3 to 6 functionalities and a mass average molecular weight Mw of 800 to 2500) shown in Table 1 and thermosetting resin 1 (an acrylic polymer having a glass transition temperature of approximately 100°C, a mass average molecular weight Mw of 55,000, and a hydroxyl value of 40) shown in Table 2 in a ratio of 4:1 as the main component. For thermosetting resin 1, hardener 1 shown in Table 3 was used. [Prescription] Coating agent B was prepared by mixing the following additives with 100 parts by mass of the above-mentioned main agent. Hardener 1:5 parts by weight Photopolymerization initiator "Omnirad184 (manufactured by IGM Resins BV)": 2 parts by mass Further, the same ultraviolet absorber, light stabilizer, diluting solvent and gloss regulator as those in the above coating agent A were mixed in the same proportions as those in the above coating agent A.
[0135] <Paint C> [Main ingredient] Coating agent C was composed of thermosetting resin 2 (an acrylic polymer having a mass average molecular weight Mw of 70,000 and a hydroxyl value of 38) shown in Table 2 as a main component. For thermosetting resin 2, curing agent 1 described above was used as a curing agent. [Prescription] Coating agent B was prepared by mixing the following additives with 100 parts by mass of the above-mentioned main agent. Hardener 1:5 parts by weight Coating agent C was prepared by mixing the same UV absorber, light stabilizer, dilution solvent and gloss regulator as in coating agent A in the same amounts per 100 parts of the base agent.
[0136] <Paint D> [Main ingredient] Coating agent D was composed mainly of a resin material prepared by mixing ionizing radiation curing resin 3 shown in Table 1 (a trifunctional acrylate compound with a mass average molecular weight Mw of 2400) and thermosetting resin 3 shown in Table 2 (an acrylic polymer with a glass transition temperature of approximately 50°C, a mass average molecular weight Mw of 140,000, and a hydroxyl value of 40) in a 1:1 ratio. [Prescription] Coating agent D was prepared by mixing the following additives with 100 parts by mass of the main agent. Hardener 2:5 parts by weight Further, the same ultraviolet absorber, light stabilizer, diluting solvent and gloss regulator as those in the above coating agent A were mixed in the same proportions as those in the above coating agent A.
[0137] <Painting agent E> [Main ingredient] Coating agent E was composed of ionizing radiation curable resin 4 shown in Table 1 (an acrylate compound having 10 functional groups and a mass average molecular weight Mw of 4900) as the main component. [Prescription] Coating agent E was prepared by mixing the same photopolymerization initiator, UV absorber, light stabilizer, dilution solvent and gloss regulator as coating agent B in the same mixing ratios as coating agent B above, per 100 parts by mass of the main component.
[0138] <Painting material F> [Main ingredient] Coating agent F was composed mainly of a resin material prepared by mixing ionizing radiation curing resin 5 shown in Table 1 (a trifunctional acrylate compound with a mass average molecular weight Mw of 3500) and thermosetting resin 4 shown in Table 2 (an acrylic polymer with a glass transition temperature of approximately 50°C, a mass average molecular weight Mw of 20,000, and a hydroxyl value of 135) in a 1:1 ratio. [Prescription] Coating agent F was prepared by mixing the following additives with 100 parts by mass of the main agent. Hardener 2:5 parts by weight Further, the same photopolymerization initiator, ultraviolet absorber, light stabilizer, diluting solvent and gloss regulator as those in the above coating agent B were mixed in the same proportions as those in the above coating agent B.
[0139] <Paint G> Coating agent G was composed of ionizing radiation curable resin 6 shown in Table 1 (an acrylate compound having seven functional groups and a mass average molecular weight Mw of 4900) as the main component. [Prescription] Coating agent G was prepared by mixing the same photopolymerization initiator, UV absorber, light stabilizer, dilution solvent and gloss regulator as coating agent B in the same mixing ratios as coating agent B above, per 100 parts by mass of the main component.
[0140] In this embodiment, polypropylene resins A to D were used as the resin material for forming the transparent resin layer. In this embodiment, the hardness (MSE resistance value MA 2-1 , MSE resistance value MB 2-1 , Erosion rate EA 2-1 , erosion rate EB 2-1 ) was controlled.
[0141] [Polypropylene resin A] Random polypropylene resin "F219DA" (Prime Polymer Co., Ltd.), MFR 8.0g / 10Min.) Extrusion temperature: 200℃ Cooling roll water temperature during film formation: 25~50℃
[0142] [Polypropylene resin B] Polyolefin thermoplastic elastomer "F3740" (Prime Polymer Co., Ltd.), MFR 4.5g / 10Min.) Extrusion temperature: 220℃ Cooling roll water temperature during film formation: 25~40℃
[0143] [Polypropylene resin C] Highly crystalline homopolypropylene resin "F109V" (Prime Polymer Co., Ltd., MFR 30.0g / 10Min.) Extrusion temperature: 200-230℃ Cooling roll water temperature during film formation: 25-65℃
[0144] [Polypropylene resin D] Homopolypropylene resin "F730NV" (Prime Polymer Co., Ltd., MFR 6.2g / 10Min.) Extrusion temperature: 200-230℃ Cooling roll water temperature during film formation: 25-65℃
[0145] Example 1 A wood grain pattern was gravure printed on a polyethylene base film (thickness 70 μm) having hiding properties as the base film layer 7 using a two-component urethane ink (V180; manufactured by Toyo Ink Co., Ltd.) to form a picture pattern layer 6 (thickness 3 μm). Further, an adhesive (Takelac A540; manufactured by Mitsui Chemicals, Inc.) (thickness 2 μm) was applied as the adhesive layer 5 to obtain an MSE resistance value MA 2-1 2.0g / μm, MSE resistance value MB 2-1 A transparent resin layer 1 having a hardness adjusted to 0.2 g / μm was then dry laminated. The transparent resin layer 1 was formed from a resin material obtained by blending various additives with polypropylene resin B. More specifically, a resin material obtained by blending 0.5 parts by mass of a hindered phenol-based antioxidant (Irganox 1010; manufactured by BASF), 0.5 parts by mass of a triazine-based ultraviolet absorber (CYASORB UV-1164; manufactured by SUNCHEM), and 0.5 parts by mass of a NOR-type light stabilizer (Tinuvin XT850 FF; manufactured by BASF) with respect to 100 parts by mass of polypropylene resin B was extruded using a melt extruder to form a transparent resin sheet having a thickness of 90 μm to be used as the transparent resin layer 1. For the transparent resin layer 1, the extrusion temperature of the polypropylene resin B was set to 220° C., and the cooling roll water temperature during film formation was set to 25° C. as process controls. 2-1 2.0g / μm, MSE resistance value MB 2-1 A transparent resin layer 1 having a thickness of 0.2 g / μm was formed.
[0146] Furthermore, a surface protective layer 4 (thickness: 5 μm) was formed by coating on the transparent resin layer 1 using coating agent D. By using coating agent D, the hardness of the surface protective layer 4 was adjusted so that the MSE resistance value MA1 was 0.06 g / μm and the MSE resistance value MB1 was 0.3 g / μm. The surface protective layer 4 was hardened by EB irradiation. In this manner, the decorative sheet 10 of Example 1 was obtained.
[0147] Example 2 The decorative sheet 10 of Example 2 was obtained in the same manner as in Example 1, except that the hardness of the surface protective layer 4 was adjusted by using coating agent C on the transparent resin layer 1 so that the MSE resistance value MA1 was 0.3 g / μm and the MSE resistance value MB1 was 0.4 g / μm. The curing method for the surface protective layer 4 was thermal curing.
[0148] Example 3 The decorative sheet 10 of Example 3 was obtained in the same manner as in Example 1, except that the hardness of the surface protective layer 4 was adjusted by using coating agent B on the transparent resin layer 1 so that the MSE resistance value MA1 was 1.3 g / μm and the MSE resistance value MB1 was 0.6 g / μm. The curing method for the surface protective layer 4 was UV irradiation.
[0149] Example 4 The decorative sheet 10 of Example 4 was obtained in the same manner as in Example 1, except that the hardness of the surface protective layer 4 was adjusted by using coating agent E on the transparent resin layer 1 so that the MSE resistance value MA1 was 1.9 g / μm and the MSE resistance value MB1 was 9.9 g / μm. The curing method for the surface protective layer 4 was UV irradiation.
[0150] Example 5 The decorative sheet 10 of Example 5 was obtained in the same manner as in Example 1, except that the hardness of the surface protective layer 4 was adjusted by using coating agent A on the transparent resin layer 1 so that the MSE resistance value MA1 was 0.6 g / μm and the MSE resistance value MB1 was 1.9 g / μm. The curing method for the surface protective layer 4 was EB irradiation.
[0151] Example 6 Polypropylene resin A is used as the resin constituting the transparent resin layer 1, and the MSE resistance value MA 2-1 is 1.0g / μm, MSE resistance value MB 2-1 A decorative sheet 10 of Example 6 was obtained in the same manner as in Example 2, except that the hardness of the transparent resin layer 1 was adjusted so that the hardness was 0.1 g / μm. In addition, for the transparent resin layer 1, the extrusion temperature of the polypropylene resin A was set to 200° C., and the cooling roll water temperature during film formation was set to 40° C. as process controls. 2-1 is 1.0g / μm, MSE resistance value MB 2-1 A transparent resin layer 1 having a thickness of 0.1 g / μm was formed.
[0152] Example 7 The transparent resin layer 1 is made of polypropylene resin C, and the MSE resistance value MA 2-1 20.0g / μm, MSE resistance value MB 2-1 A decorative sheet 10 of Example 7 was obtained in the same manner as in Example 2, except that the hardness of the transparent resin layer 1 was adjusted so that the hardness was 2.0 g / μm. In addition, as process control for the transparent resin layer 1, the extrusion temperature of the polypropylene resin C was set to 200° C., and the cooling roll water temperature during film formation was set to 60° C. As a result, the MSE resistance value MA 2-1 20.0g / μm, MSE resistance value MB 2-1 A transparent resin layer 1 having a thickness of 2.0 g / μm was formed.
[0153] Example 8 The transparent resin layer 1 is made of polypropylene resin C, and the MSE resistance value MA 2-1 15.0g / μm, MSE resistance value MB 2-1 A decorative sheet 10 of Example 8 was obtained in the same manner as in Example 2, except that the hardness of the transparent resin layer 1 was adjusted so that the hardness was 1.0 g / μm. In addition, as process control for the transparent resin layer 1, the extrusion temperature of the polypropylene resin C was set to 200° C., and the cooling roll water temperature during film formation was set to 40° C. As a result, the MSE resistance value MA 2-1 15.0g / μm, MSE resistance value MB 2-1 A transparent resin layer 1 having a thickness of 1.0 g / μm was formed.
[0154] Example 9 A wood grain pattern was gravure printed on a polyethylene base film (thickness 70 μm) having hiding properties as the base film layer 7 using a two-component urethane ink (V180; manufactured by Toyo Ink Co., Ltd.) to form a picture pattern layer 6 (thickness 3 μm). Further, an adhesive (Takelac A540; manufactured by Mitsui Chemicals, Inc.) (thickness 2 μm) was applied as the adhesive layer 5 to obtain an MSE resistance value MA 2-2 1.0g / μm, MSE resistance value MB 2-2 A transparent resin layer 2 having a hardness adjusted to 0.1 g / μm was then dry laminated.
[0155] The transparent resin layer 2 was formed of a resin material obtained by blending various additives with polypropylene resin A. More specifically, a resin material obtained by blending 0.5 parts by mass of a hindered phenol-based antioxidant (Irganox 1010; manufactured by BASF), 0.5 parts by mass of a triazine-based ultraviolet absorber (CYASORB UV-1164; manufactured by SUNCHEM), and 0.5 parts by mass of a NOR-type light stabilizer (Tinuvin XT850 FF; manufactured by BASF) with respect to 100 parts by mass of polypropylene resin A was extruded using a melt extruder to form a transparent resin sheet having a thickness of 20 μm to be used as the transparent resin layer 2. For the transparent resin layer 2, the extrusion temperature of polypropylene resin A was set to 200° C., and the cooling roll water temperature during film formation was set to 40° C. as process control. As a result, the MSE resistance value MA 2-2 is 1.0g / μm, MSE resistance value MB 2-2 A transparent resin layer 2 having a thickness of 0.1 g / μm was formed.
[0156] Furthermore, the MSE resistance value MA 2-1 2.0g / μm, MSE resistance value MB 2-1The transparent resin layer 1, the hardness of which was adjusted to 0.2 g / μm, was dry laminated. The transparent resin layer 1 was formed of a resin material obtained by blending various additives with polypropylene resin B. More specifically, a resin material obtained by blending 0.5 parts by mass of a hindered phenol-based antioxidant (Irganox 1010; manufactured by BASF), 0.5 parts by mass of a triazine-based ultraviolet absorber (CYASORB UV-1164; manufactured by SUNCHEM), and 0.5 parts by mass of a NOR-type light stabilizer (Tinuvin XT850 FF; manufactured by BASF) with respect to 100 parts by mass of polypropylene resin B was extruded using a melt extruder to form a transparent resin sheet having a thickness of 70 μm to be used as the transparent resin layer 1. In this example, the process control (extrusion temperature, cooling roll water temperature during film formation) of polypropylene resin B was the same as in Example 2, and the MSE resistance value MA 2-1 2.0g / μm, MSE resistance value MB 2-1 A transparent resin layer 1 having a thickness of 0.2 g / μm was formed.
[0157] Moreover, the surface protective layer 4 had the same structure as in Example 2. In this way, a decorative sheet 10 of Example 9 having two transparent resin layers was obtained.
[0158] Example 10 Polypropylene resin B is used as the resin constituting the transparent resin layer 2, and the MSE resistance value MA 2-2 2.0g / μm, MSE resistance value MB 2-2 A decorative sheet 10 of Example 10 was obtained in the same manner as in Example 9, except that the hardness of the transparent resin layer 2 was adjusted so that the hardness was 0.2 g / μm. In addition, as process control for the transparent resin layer 2, the extrusion temperature of the polypropylene resin B was set to 220° C., and the cooling roll water temperature during film formation was set to 25° C. As a result, the MSE resistance value MA 2-2 2.0g / μm, MSE resistance value MB 2-2 A transparent resin layer 2 having a thickness of 0.2 g / μm was formed.
[0159] Example 11 The transparent resin layer 2 is made of polypropylene resin D, and the MSE resistance value MA 2-28.0g / μm, MSE resistance value MB 2-2 A decorative sheet 10 of Example 11 was obtained in the same manner as in Example 9, except that the hardness of the transparent resin layer 2 was adjusted so that the hardness was 0.8 g / μm. In addition, as process control for the transparent resin layer 2, the extrusion temperature of the polypropylene resin D was set to 230° C., and the cooling roll water temperature during film formation was set to 25° C. As a result, the MSE resistance value MA 2-2 8.0g / μm, MSE resistance value MB 2-2 A transparent resin layer 2 having a thickness of 0.8 g / μm was formed.
[0160] Example 12 The transparent resin layer 2 is made of polypropylene resin C, and the MSE resistance value MA 2-2 20.0g / μm, MSE resistance value MB 2-2 A decorative sheet 10 of Example 12 was obtained in the same manner as in Example 9, except that the hardness of the transparent resin layer 2 was adjusted so that the hardness was 2.0 g / μm. In addition, as process control for the transparent resin layer 2, the extrusion temperature of the polypropylene resin C was set to 230° C., and the cooling roll water temperature during film formation was set to 60° C. As a result, the MSE resistance value MA 2-2 20.0g / μm, MSE resistance value MB 2-2 A transparent resin layer 2 having a thickness of 2.0 g / μm was formed.
[0161] Example 13 The transparent resin layer 2 is made of polypropylene resin C, and the MSE resistance value MA 2-2 15.0g / μm, MSE resistance value MB 2-2 A decorative sheet 10 of Example 13 was obtained in the same manner as in Example 9, except that the hardness of the transparent resin layer 2 was adjusted so that the hardness was 1.0 g / μm. In addition, as process control for the transparent resin layer 2, the extrusion temperature of the polypropylene resin C was set to 230° C., and the cooling roll water temperature during film formation was set to 40° C. As a result, the MSE resistance value MA 2-2 15.0g / μm, MSE resistance value MB 2-2 A transparent resin layer 2 having a thickness of 1.0 g / μm was formed.
[0162] Example 14 The decorative sheet 10 of Example 14 was obtained in the same manner as in Example 1, except that the hardness of the surface protective layer 4 was adjusted by using coating agent F on the transparent resin layer 1 so that the MSE resistance value MA1 was 0.04 g / μm and the MSE resistance value MB1 was 0.1 g / μm. The curing method for the surface protective layer 4 was UV irradiation.
[0163] Example 15 The decorative sheet 10 of Example 15 was obtained in the same manner as in Example 1, except that the hardness of the surface protective layer 4 was adjusted by using coating agent G on the transparent resin layer 1 so that the MSE resistance value MA1 was 2.1 g / μm and the MSE resistance value MB1 was 10.5 g / μm. The curing method for the surface protective layer 4 was UV irradiation.
[0164] Example 16 Polypropylene resin A is used as the resin constituting the transparent resin layer 1, and the MSE resistance value MA 2-1 0.8g / μm, MSE resistance value MB 2-1 A decorative sheet 10 of Example 16 was obtained in the same manner as in Example 2, except that the hardness of the transparent resin layer 1 was adjusted so that the hardness was 0.09 g / μm. In addition, for the transparent resin layer 1, the extrusion temperature of the polypropylene resin A was set to 200° C., and the cooling roll water temperature during film formation was set to 25° C. as process controls. 2-1 0.8g / μm, MSE resistance value MB 2-1 A transparent resin layer 1 having a thickness of 0.09 g / μm was formed.
[0165] (Example 17) The transparent resin layer 1 is made of polypropylene resin C, and the MSE resistance value MA 2-1 21.0g / μm, MSE resistance value MB 2-1 A decorative sheet 10 of Example 17 was obtained in the same manner as in Example 2, except that the hardness of the transparent resin layer 1 was adjusted so that the hardness was 2.5 g / μm. In addition, as process control for the transparent resin layer 1, the extrusion temperature of the polypropylene resin C was 230° C., and the cooling roll water temperature during film formation was 65° C. As a result, the MSE resistance value MA2-1 21.0g / μm, MSE resistance value MB 2-1 A transparent resin layer 1 having a thickness of 2.5 g / μm was formed.
[0166] (Example 18) Polypropylene resin A was used as the resin constituting the transparent resin layer 2, and the MSE resistance value MA 2-2 0.8g / μm, MSE resistance value MB 2-2 A decorative sheet 10 of Example 18 was obtained in the same manner as in Example 9, except that the hardness of the transparent resin layer 2 was adjusted so that the hardness was 0.09 g / μm. In addition, for the transparent resin layer 2, the extrusion temperature of the polypropylene resin A was set to 200° C., and the cooling roll water temperature during film formation was set to 25° C. as process controls. 2-2 0.8g / μm, MSE resistance value MB 2-2 A transparent resin layer 2 having a viscosity of 0.09 g / μm was formed.
[0167] (Example 19) The transparent resin layer 2 is made of polypropylene resin C, and the MSE resistance value MA 2-2 21.0g / μm, MSE resistance value MB 2-2 A decorative sheet 10 of Example 19 was obtained in the same manner as in Example 12, except that the hardness of the transparent resin layer 2 was adjusted so that the hardness was 2.5 g / μm. In addition, as process control for the transparent resin layer 2, the extrusion temperature of the polypropylene resin C was 230° C., and the cooling roll water temperature during film formation was 65° C. As a result, the MSE resistance value MA 2-2 21.0g / μm, MSE resistance value MB 2-2 A transparent resin layer 2 having a thickness of 2.5 g / μm was formed.
[0168] Comparative Example 1 The decorative sheet 10 of Comparative Example 1 was obtained in the same manner as in Example 17, except that the hardness of the surface protective layer 4 was adjusted by using coating agent F on the transparent resin layer 1 so that the MSE resistance value MA1 was 0.04 g / μm and the MSE resistance value MB1 was 0.1 g / μm. The curing method for the surface protective layer 4 was UV irradiation.
[0169] Comparative Example 2 A decorative sheet 10 of Comparative Example 2 was obtained in the same manner as in Example 16, except that the hardness of the surface protective layer 4 was adjusted by using coating agent G on the transparent resin layer 1 so that the MSE resistance value MA1 was 2.1 g / μm and the MSE resistance value MB1 was 10.5 g / μm. The curing method for the surface protective layer 4 was UV irradiation.
[0170] Comparative Example 3 A decorative sheet 10 of Comparative Example 3 was obtained in the same manner as in Example 19, except that the hardness of the surface protective layer 4 was adjusted by using coating agent F on the transparent resin layer 1 so that the MSE resistance value MA1 was 0.04 g / μm and the MSE resistance value MB1 was 0.1 g / μm. The curing method for the surface protective layer 4 was UV irradiation.
[0171] Comparative Example 4 A decorative sheet 10 of Comparative Example 4 was obtained in the same manner as in Example 18, except that the hardness of the surface protective layer 4 was adjusted by using coating agent G on the transparent resin layer 1 so that the MSE resistance value MA1 was 2.1 g / μm and the MSE resistance value MB1 was 10.5 g / μm. The curing method for the surface protective layer 4 was UV irradiation.
[0172] (evaluation) The decorative sheets of Examples 1 to 19 and Comparative Examples 1 to 4 obtained by the above method were attached to a wood substrate using a urethane adhesive to produce decorative materials using the decorative sheets of each Example and Comparative Example. Then, the decorative materials were evaluated for scratch resistance, abrasion resistance, and post-processability as described below.
[0173] <Scratch resistance evaluation> The Hoffman scratch test was selected as the method for evaluating scratch resistance. The Hoffman scratch test was carried out using a Hoffman scratch hardness tester (manufactured by BYK-Gardner) by scratching the surface of the above decorative material using the decorative sheets of each Example and Comparative Example at a constant speed with a load of 200g to 2000g, with a test length of 5cm per 200g, and the load at which damage to the surface of the decorative sheet occurred was recorded. 〇: Hoffman Scratch 1000g or more △: Hoffman Scratch 400g to 800g ×: Hoffman scratch 200g or less In addition, a rating of "△" or above is deemed to be at a practical level and is therefore rated as "pass."
[0174] <Abrasion resistance evaluation> A steel wool rubbing (abrasion) test was selected as the method for evaluating scratch resistance. In the steel wool rubbing (abrasion) test, steel wool was placed in contact with the surface (decorative sheet) of the decorative material of each Example and Comparative Example and fixed using a jig, and 500 g / cm 2 The sheet was rubbed 50 times back and forth at a constant speed with a load of 100 mm, and the presence or absence of damage to the surface of the decorative sheet was visually judged. The steel wool used was Bonstar #0 (manufactured by Japan Steel Wool Co., Ltd.), rolled into 1 cm squares. ◎: No change in gloss or scratches 〇: Slight change in gloss can be seen, but no scratches △: There is a change in gloss and slight scratches ×: Change in gloss and numerous scratches In this steel wool abrasion test, "◎", "◯" and "△" were rated as passing.
[0175] <Machining characteristics (post-processability)> The processing characteristics were evaluated using the following two methods: (1) and (2). (1) A two-part water-based emulsion adhesive ("Rikabond" manufactured by Chuo Rika Kogyo Co., Ltd. (weight ratio BA-10L / BA-11B = 100:2.5)) was applied in a wet state at 100 g / m on the surface of 3 mm thick MDF (hardwood) used as the base material for the fittings. 2 After coating, a decorative sheet of each Example and Comparative Example was attached thereto and cured for 24 hours to obtain a decorative door and window material of each Example and Comparative Example. These decorative window fittings were V-cut and their appearance was checked by visually inspecting the top of the bent part. The V-cut process involved making a V-shaped groove from the side of the decorative window fitting material where the decorative sheet was not attached to the boundary where the base material and the decorative sheet were attached to prevent scratches on the decorative sheet. Next, the fitting base material was folded 90 degrees along the V-shaped groove so that the surface to which the decorative sheet of each Example and Comparative Example was attached formed a mountain fold. Next, the folded portions of the surface of the decorative sheet were visually and optically observed to see whether whitening or cracks had occurred, and the post-processing resistance was evaluated.
[0176] (2) The decorative sheet was folded at room temperature in a 180° direction so that the surface protective layer was exposed, and the appearance was evaluated visually.
[0177] Both (1) and (2) above were evaluated according to the following evaluation criteria, and the results are shown in Table 4. In addition, if the evaluation is between "◎" and "△", it is evaluated that there is no problem in practical use. ◎: No cracks or whitening of the surface protective layer were observed at the top of the folded portion by any observation method. ○: When observed under an optical microscope at the top of the bent part, there is some slight cracking or whitening of the surface protection layer, but this is not noticeable to the naked eye. △: When observed under an optical microscope at the top of the bent portion, cracks and whitening of the surface protective layer occur, but cannot be detected by visual inspection. ×: Significant cracking and whitening of the surface protective layer was observed even with the naked eye at the top of the bent portion.
[0178] As described above, if the decorative sheet 10 is a laminate having a surface protective layer 4 on an original layer 7, the surface protective layer 4 comprises a cured product of a curable resin composition, the MSE resistance value MA1 obtained from the erosion rate EA1 measured using polygonal alumina particles having an average particle size (D50) of 0.3 μm is in the range of 0.05 g / μm or more and 2.0 g / μm or less, and the MSE resistance value MB1 obtained from the erosion rate EB1 measured using spherical silica particles having an average particle size (D50) of 1.1 μm is in the range of 0.2 g / μm or more and 10.0 g / μm or less, it can be seen that the scratch resistance, abrasion resistance, and processing characteristics (post-processability) all have performance that is sufficient for practical use.
[0179] The decorative sheet 10 is a laminate including a transparent resin layer 1 and a surface protective layer 4, The transparent resin layer 1 (11) is composed of a single layer or multiple layers, and in all of the layers constituting the transparent resin layer 1 (11), if the MSE resistance value MA2 obtained from the erosion rate EA2 measured using polygonal alumina particles having an average particle size (D50) of 1.2 μm is in the range of 1.0 g / μm or more and 20.0 g / μm or less, and the MSE resistance value MB2 obtained from the erosion rate EB2 measured using spherical alumina particles having an average particle size (D50) of 3.0 μm is in the range of 0.1 g / μm or more and 2.0 g / μm or less, then it can be seen that the scratch resistance and processing characteristics (post-processability) are all sufficient to provide sufficient performance for practical use.
[0180] Table 4 below shows the configurations of the decorative sheets of the examples and comparative examples in this embodiment, as well as the evaluation results of the above-mentioned changes in appearance.
[0181] [Table 4]
[0182] Moreover, for example, this embodiment can have the following configuration. (1) A laminate having at least a surface protective layer on an original sheet, The surface protective layer contains a cured product of a curable resin composition, and the MSE resistance value MA1 obtained from the erosion rate EA1 measured using polygonal alumina particles with an average particle size (D50) of 0.3 μm is in the range of 0.05 g / μm < MA1 < 2.0 g / μm, and the MSE resistance value MB1 obtained from the erosion rate EB1 measured using spherical silica particles with an average particle size (D50) of 1.1 μm is in the range of 0.2 g / μm < MB1 < 10.0 g / μm. The laminate is characterized by this. (2) The surface protective layer has an MSE resistance value MB1 in the range of 0.2 g / μm < MB1 < 2.0 g / μm. The laminate according to (1) above is characterized by this. (3) A laminate including at least a transparent resin layer and a surface protective layer, The transparent resin layer is composed of a single layer or multiple layers. In all the layers constituting the transparent resin layer, the MSE resistance value MA2 obtained from the erosion rate EA2 measured using polygonal alumina particles with an average particle size (D50) of 1.2 μm is in the range of 1.0 g / μm < MA2 < 20.0 g / μm, and the MSE resistance value MB2 obtained from the erosion rate EB2 measured using spherical alumina particles with an average particle size (D50) of 3.0 μm is in the range of 0.1 g / μm < MB2 < 2.0 g / μm. The laminate is characterized by this. (4) The transparent resin layer has an MSE resistance value MA2 in the range of 1.0 g / μm < MA2 < 15.0 g / μm and an MSE resistance value MB2 in the range of 0.1 g / μm < MB2 < 1.0 g / μm. The laminate according to (3) above is characterized by this. (5) A woody base material, The laminate according to any one of (1) to (4) above, which is bonded to the woody base material, A decorative material characterized by including this. (6) A base material for a decorative material, The laminate according to any one of (1) to (4) above, which is bonded to the base material for a decorative material, A decorative material characterized by including this. (7) A method for manufacturing a laminate having at least a surface protection layer on a base material, wherein the surface protection layer is formed of a cured product of a curable resin composition, and an MSE resistance value MA1 obtained from an erosion rate EA1 measured using polygonal alumina particles having an average particle diameter (D50) of 0.3 μm is set within a range of 0.05 g / μm < MA1 < 2.0 g / μm, and an MSE resistance value MB1 obtained from an erosion rate EB1 measured using spherical silica particles having an average particle diameter (D50) of 1.1 μm is set within a range of 0.2 g / μm < MB1 < 10.0 g / μm. A method for manufacturing a laminate characterized by this. (8) A method for manufacturing a laminate including at least a transparent resin layer and a surface protection layer, wherein the transparent resin layer is composed of a single layer or multiple layers, and in all layers constituting the transparent resin layer, an MSE resistance value MA2 obtained from an erosion rate EA2 measured using polygonal alumina particles having an average particle diameter (D50) of 1.2 μm is set within a range of 1.0 g / μm < MA2 < 20.0 g / μm, and an MSE resistance value MB2 obtained from an erosion rate EB2 measured using spherical alumina particles having an average particle diameter (D50) of 3.0 μm is set within a range of 0.1 g / μm < MB2 < 2.0 g / μm. A method for manufacturing a laminate characterized by this. (9) A method for selecting a material for a laminate having at least a surface protection layer on a base material, wherein the surface protection layer is formed of a cured product of a curable resin composition, and an MSE resistance value MA1 obtained from an erosion rate EA1 measured using polygonal alumina particles having an average particle diameter (D50) of 0.3 μm is set within a range of 0.05 g / μm < MA1 < 2.0 g / μm, and an MSE resistance value MB1 obtained from an erosion rate EB1 measured using spherical silica particles having an average particle diameter (D50) of 1.1 μm is set within a range of 0.2 g / μm < MB1 < 10.0 g / μm. A method for selecting a material for a laminate characterized by this. (10) A method for selecting a material for a laminate including at least a transparent resin layer and a surface protection layer, The transparent resin layer is composed of a single layer or multiple layers. In all the layers constituting the transparent resin layer, the MSE resistance value MA2 obtained from the erosion rate EA2 measured using polygonal alumina particles with an average particle size (D50) of 1.2 μm is set within the range of 1.0 g / μm < MA2 < 20.0 g / μm, and the MSE resistance value MB2 obtained from the erosion rate EB2 measured using spherical alumina particles with an average particle size (D50) of 3.0 μm is set within the range of 0.1 g / μm < MB2 < 2.0 g / μm. A method for selecting materials for a laminate, characterized by this setting.
Explanation of symbols
[0183] 1, 2, 11 Transparent resin layer 1a Embossed pattern 3 Concealing layer 4 Surface protection layer 5 Adhesive layer 6 Pattern layer 7 Base material layer 8 Easy - adhesion layer 10, 20 Decorative sheet 15 Adhesive 16 Wood - like substrate 100 Decorative material
Claims
1. A laminate having at least a surface protective layer on an original sheet, The surface protective layer contains a cured product of a curable resin composition, and the erosion rate EA measured using polygonal alumina particles having an average particle size (D50) of 0.3 μm 1 The MSE resistance value obtained from MA 1 0.05g / μm<MA 1 <2.0 g / μm and erosion rate EB measured using spherical silica particles with an average particle size (D50) of 1.1 μm 1 The MSE resistance value MB obtained from 1 is 0.2g / μm<MB 1 <10.0 g / μm.
2. The surface protection layer has the MSE resistance value M 1 is 0.2g / μm<MB 1 2. The laminate of claim 1, wherein the thickness is in the range of <2.0 g / μm.
3. A laminate including at least a transparent resin layer and a surface protective layer, The transparent resin layer is composed of a single layer or multiple layers, and in all layers constituting the transparent resin layer, the erosion rate EA measured using polygonal alumina particles having an average particle size (D50) of 1.2 μm is 2 The MSE resistance value obtained from MA 2 1.0g / μm<MA 2 <20.0 g / μm and the erosion rate EB measured using spherical alumina particles having an average particle size (D50) of 3.0 μm 2 The MSE resistance value MB obtained from 2 is 0.1 g / μm < MB 2 <2.0 g / μm.
4. The transparent resin layer has an MSE resistance value MA 2 1.0g / μm<MA 2 <15.0 g / μm, and the MSE resistance value M 2 is 0.1 g / μm < MB 2 4. The laminate of claim 3, wherein the thickness is in the range of <1.0 g / μm.
5. A wood base material; The laminate according to any one of claims 1 to 4, which is bonded to the wood base material; A decorative material comprising:
6. A base material for a cosmetic material, The laminate according to any one of claims 1 to 4, which is bonded to the substrate for decorative material; A decorative material comprising:
7. A method for producing a laminate having at least a surface protective layer on an original sheet, comprising the steps of: The surface protective layer is formed from a cured product of a curable resin composition, and the erosion rate EA is measured using polygonal alumina particles having an average particle size (D50) of 0.3 μm. 1 The MSE resistance value obtained from MA 1 0.05g / μm<MA 1 <2.0 g / μm and measured using spherical silica particles with an average particle size (D50) of 1.1 μm. 1 The MSE resistance value MB obtained from 1 0.2g / μm<MB 1 <10.0 g / μm.
8. A method for producing a laminate including at least a transparent resin layer and a surface protective layer, comprising the steps of: The transparent resin layer is composed of a single layer or multiple layers, and the erosion rate EA measured using polygonal alumina particles having an average particle size (D50) of 1.2 μm in all layers constituting the transparent resin layer 2 The MSE resistance value obtained from MA 2 1.0 g / μm<MA 2 <20.0 g / μm and the erosion rate EB measured using spherical alumina particles having an average particle size (D50) of 3.0 μm 2 The MSE resistance value MB obtained from 2 0.1 g / μm <MB 2 <2.0 g / μm range.
9. A method for selecting a material for a laminate having at least a surface protective layer on an original sheet, comprising the steps of: The surface protective layer is formed from a cured product of a curable resin composition, and the erosion rate EA is measured using polygonal alumina particles having an average particle size (D50) of 0.3 μm. 1 The MSE resistance value obtained from MA 1 0.05g / μm<MA 1 <2.0 g / μm and the erosion rate EB measured using spherical silica particles with an average particle size (D50) of 1.1 μm 1 The MSE resistance value MB obtained from 1 0.2g / μm<MB 1 <10.0 g / μm range.
10. A method for selecting a material for a laminate including at least a transparent resin layer and a surface protective layer, comprising the steps of: The transparent resin layer is composed of a single layer or multiple layers, and the erosion rate EA measured using polygonal alumina particles having an average particle size (D50) of 1.2 μm in all layers constituting the transparent resin layer 2 The MSE resistance value obtained from MA 2 1.0 g / μm<MA 2 <20.0 g / μm and the erosion rate EB measured using spherical alumina particles having an average particle size (D50) of 3.0 μm 2 The MSE resistance value MB obtained from 2 0.1 g / μm <MB 2 <2.0 g / μm range.
Citation Information
Patent Citations
Decorative sheet
JP2008238444A
Decorative sheet and decorative material
JP2014188941A